Grievance Redress Mechanisms in the Health Sector in Mozambique - POTENCIAR (POTENCIAR, 2023)
Context: This research stemmed from learning and changes that occurred in the intervention strategy and budget of the POTENCIAR programme. In consultations and meetings between the Programme Management Unit (UGP) and various actors operating in this area, POTENCIAR’s partners identified — in a participatory and inclusive manner — the issue of grievance redress mechanisms as a problem that they can intervene on within the context of Pro-Accountability Initiatives (PAIs). Taking this perspective , POTENCIAR conceived the present research on mechanisms for complaining about and denouncing poor standards in maternity services. Objectives: The objective of this study was to understand the complaints and grievances management system available to users in the health sector. The insights gained from this study will subsequently feed back into revision s to POTENCIAR’s theory of change and theory of action. The research included mapping the flow of the complaint channel ling process; identifying the motives, capacities, and opportunities for the health authorities to implement the system of mechanisms for redressing complaints; an analysis of how the perspectives of users are perceived, considered, and rejected by health authorities; and, finally, an analysis of the extent to which existing grievance mechanisms are used, including the opportunities, capacities, and motivations for using them.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; governance / governação; health / saúde; mecanismos de reclamação / grievance redress mechanisms

A aceleração da financeirização: respostas das instituições financeiras internacionais à pandemia da COVID-19 em Moçambique - Barroso, Edgar; Castel-Branco, Ruth; Monjane, Boaventura (Desafios para Moçambique 2022, 2022)
O estudo conclui que as IFI aproveitaram este momento de crise para acelerar a financeirização do desenvolvimento; porém, também ilustra a resistência tanto do Estado como da sociedade civil. Se essas formas de resistência podem ou não contribuir para a construção de um Estado desenvolvido robusto depende do poder dos movimentos sociais globalizados para reaver o controlo e sacá-lo das garras do capitalismo financeiro. A primeira secção situa as respostas políticas do FMI e do Banco Mundial à pandemia da covid-19, numa análise histórica. Em 1987, Moçambique embarcou no seu primeiro programa de ajustamento estrutural, liberalizando a economia e eliminando impostos e tarifas; privatizando serviços públicos, empresas e activos; e desregulando as protecções sobre o consumidor e o trabalho. Essas medidas resultaram em cortes maciços na despesa, austeridade e dívida pública. A dívida de Moçambique foi subsequentemente cancelada, mas o FMI continuou a controlar a sua economia através do Instrumento de Apoio às Políticas. Actualmente, o Banco Mundial financia projectos que rondam os 3,7 mil milhões de dólares, ou o equivalente ao orçamento anual de Moçambique. O sector agrícola representa 14% do investimento e a protecção social, 9%. A segunda secção demonstra como o Banco Mundial utilizou a pandemia da covid-19 para impor a sua agenda de protecção social de duas formas importantes. Em primeiro lugar, substituindo a ideia de direitos universais por concessões altamente selectivas, de curto prazo e residuais ao arrepio das causas na raiz da pobreza e da desigualdade. Segundo argumentavam, as necessidades de longo prazo poderiam ser abordadas mais eficazmente pela diversificação dos meios de subsistência e a incorporação dos agregados familiares em situação de pobreza nos mercados financeiros através do crédito e da dívida. Em segundo lugar, tentando financiar as transferências monetárias pela externalização de sistemas de pagamento a prestadores de serviços financeiros. Embora esses condicionalismos se tenham revelado impossíveis de implementar e o Governo tenha acabado por ter de internalizar o programa, todo esse fiasco teve um custo material e humano considerável para os Moçambicanos. A terceira secção explora a abordagem do Banco Mundial à agricultura. Apesar de reconhecer que Moçambique tem uma lei da terra progressista, há muito que o Banco Mundial faz pressão pela colateralização da terra, a incorporação dos agricultores em cadeias produtos de base globais e a expansão da agricultura de grande escala, orientada para o mercado. Contudo, como ilustra a destruição da indústria do caju, os resultados são muitas vezes contraditórios. Recentemente, o Banco Mundial reorientou o seu apoio para a agricultura de pequena escala, adoptando o projecto Sustenta. O apoio aos pequenos proprietários e agricultores camponeses tem-se articulado com a privatização e a colateralização da terra. Com efeito, o lançamento do Sustenta coincide com a revisão da própria lei da terra que tinham elogiado como sendo progressista. Como conclui o capítulo, a pandemia criou uma oportunidade para o Banco Mundial acelerar a financeirização pela instrumentalização de empréstimos e subvenções. Isto levou à tentativa de expropriação do Estado moçambicano e da sua população através da externalização das funções do Estado e da privatização dos activos do Estado. Não obstante, os momentos de crise criam janelas de oportunidade para reorientar a política e a acção no sentido da construção de um estado desenvolvido. O capítulo insta a uma maior articulação entre os movimentos sociais - sejam eles sedeados no lar, no campo, na esquina, ou na fábrica - para unir forças contra a onda de expropriações, exploração e neoliberalismo tardio. Além disso, apela a que se reanime o movimento da justiça global para que seja possível responsabilizar as instituições financeiras internacionais
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19

Avaliação do Impacto da Subcomponente Subsídio para Crianças dos 0 aos 2. Componente de Subsídio para Criança do Programa Subsídio Social Básico na Província de Nampula em Moçambique Relatório da Pesquisa Final (24 meses) - Bonilla, Juan; Castro-Zarzur, Rosa; Seidenfeld, David; Peterman, Amber; Bruckauf, Zlata (American Institutes for Research e UNICEF, 2022)
Este relatório fornece os resultados finais da avaliação do Subsídio para Criança 0-2 de Moçambique. O Subsídio Criança 0-2 é um subcomponente do Programa de Subsídio Social Básico (PSSB), um programa nacional liderado pelo Ministério de Gênero, Criança e Ação Social (MGCAS). A avaliação coincide com a fase de arranque da intervenção, que aconteceu até 2021 em quatro distritos seleccionados da província de Nampula. A intervenção segue uma metodologia de 'dinheiro e cuidado' e inclui três componentes: (1) transferências de dinheiro, (2) um pacote de comunicação para a mudança social e de comportamentos (CMSC) com ênfase em nutrição (3) uma gestão de casos em temas de proteção social para os mais vulneráveis. A intervenção visa reduzir a pobreza e a vulnerabilidade social, fornecendo transferências em dinheiro para as cuidadoras principais de crianças pequenas com o objetivo geral de reduzir a pobreza, melhorar o bem-estar infantil e promover o acesso a serviços sociais básicos. Além disso, o componente de cuidados da intervenção pretende abordar a proteção complexa e inter-relacionada, bem como os riscos sociais, econômicos e de saúde, que as famílias-alvo enfrentam. A intervenção começou a ser implementada em setembro de 2018, e esta avaliação fornece evidências críticas sobre sua eficácia para informar a melhor forma de expansão da intervenção.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Ilha de Moçambique; GD - Lalaua; GD - Mogincual; GD - Nacala-a-Velha; GP - Nampula; L - portuguese / português; health - maternal and child / saúde - materno-infantil; social protection / proteção social

Mulheres lutando contra o HIV/SIDA: cuidadoras de Moçambique - Casimiro, Isabel Maria; Fauré, Yves-A; Tembe, Carlota Mondlane; Mutisse, Luisa Chicamisse (Desafios para Moçambique 2022, 2022)
Moçambique é um país caracterizado por índices elevados de pobreza onde a prevalência do Vírus da Imunodeficiência Humana (HIV)/Síndrome da Imunodeficiência Adquirida (SIDA) é muito alta e a taxa de incidência ainda preocupante, e cujos meios de combate à doença são limitados e dependem, em parte, da ajuda externa. A súbita emergência e rápida expansão da covid-19, a partir do início de 2020, teve um impacto negativo nas condições de tratamento das PVHIV, que, de certa forma, sofreram uma dupla aflição. Os serviços de saúde essenciais foram afectados - prevenção, diagnóstico, tratamento, cuidados paliativos e reabilitativos, etc. - com efeitos graves nos doentes mais vulneráveis (crianças, idosos, pessoas que vivem com doenças crónicas). Com este estudo, pretendemos apresentar os resultados obtidos através da divulgação das iniciativas das mulheres junto às autoridades públicas, instituições nacionais e internacionais, agências de cooperação bilaterais, associações e ONGs moçambicanas e estrangeiras dedicadas de uma ou de outra forma à luta contra o HIV/SIDA. Finalmente, almejamos examinar as condições em que estas iniciativas poderiam ser integradas ou pelo menos aproximadas das Unidades Sanitárias que trabalham na área do HIV/SIDA.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; gender / género; health / saúde; society / sociedade

Influência das repostas interinstitucionais coordenadas a emergências e desastres de saúde pública na resposta nacional à COVID-19 em Moçambique: Estudo de caso. - Inguane, Celso; Zimba, Victor (Desafios para Moçambique 2022, 2022)
Moçambique articulou oportunamente uma resposta nacional coordenada à covid-19, com um comando claro dos níveis mais altos do Governo central, inicialmente conceptualizada pelo sector da saúde. A resposta seguiu um modelo aparentemente híbrido, baseado numa resposta humanitária rápida usada para enfrentar calamidades naturais e numa abordagem de saúde global usada para responder a eventos de saúde pública. Estas abordagens foram institucionalizadas no País ao longo de duas décadas, caracterizadas pela liderança normativa do Governo moçambicano e apoio logístico, técnico e financeiro dos parceiros de cooperação internacional, com participação limitada da sociedade civil e do empresariado local em processos de tomada de decisão sobre a concepção e implementação da resposta. Este padrão de participação ficou evidente no primeiro ano da resposta à covid-19, em Moçambique. Contudo, foi também notado como padrão da resposta global a surtos de doenças infecciosas, epidemias e pandemias entre 2002 e 2015, nos seguintes termos: «muito frequentemente, o envolvimento da comunidade tem sido uma consideração a posteriori — pouco investigado, deixado para depois até que seja demasiado tarde e implementado atabalhoadamente” (Sands, Mundaca-Shah, & Dzau, 2016). O primeiro ano da resposta à covid-19, em Moçambique, revelou igualmente a presença generalizada de múltiplos mecanismos de coordenação, profundamente permeados por competições institucionais, incluindo a coexistência de múltiplos sistemas de informação em saúde, de repositórios e protocolos que não alimentavam a rotina do sistema de informação em saúde de modo que informasse uma resposta eficaz e coordenada à covid-19. Atender a tais multiplicidades requer energia e recursos que se desviavam da gestão eficaz da resposta nacional à covid-19. A dispersa legislação nacional sobre saúde pública, que não tomou em conta as necessidades de quarentena e outras restrições ao movimento de pessoas exigidas pela resposta à covid-19, agravou estas multiplicidades. O vácuo que essa escassez criou foi preenchido por uma profusão legislativa, produzida no âmbito de um Estado de Emergência, eventualmente substituído por um Estado de Calamidade Pública. Tal contribuiu para restrições ao espaço cívico (Pereira, Forquilha, & Shankland, 2021), justificadas por lógicas de governação da saúde pública. Assim, o modelo utilizado para a coordenação do primeiro ano da resposta nacional à covid-19, em Moçambique, salienta a importância de uma complexa combinação de influências sociopolíticas e de saúde pública que moldam as respostas nacionais a emergências e desastres de saúde pública no País. Tais influências incluem a exposição a pandemias nos últimos anos (Tsuei, 2020), exposição a desastres naturais a longo-prazo (Moore, Eng, & Daniel, 2003) Mozambique suffered its worst flooding in almost 50 years: 699 people died and hundreds of thousands were displaced. Over 49 countries and 30 international non-governmental organisations provided humanitarian assistance. Coordination of disaster assistance is critical for effective humanitarian aid operations, but limited attention has been directed toward evaluating the system-wide structure of inter-organisational coordination during humanitarian operations. Network analysis methods were used to examine the structure of interorganisational relations among 65 non-governmental organisations (NGOs e a interesses institucionais locais e globais (Fassin, 2012), incluindo a secundarização do envolvimento comunitário, notado com um padrão global (Sands, Mundaca-Shah, & Dzau, 2016) também documentados em países de língua oficial portuguesa (LEIASS, 2020).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; politics / política

As relações Brasil-África no contexto da pandemia da COVID-19. Cooperação com Moçambique - Marcondes, Danilo (Desafios para Moçambique 2022, 2022)
A pandemia da covid-19 rapidamente se impôs como um dos principais, se não o principal, tema de política internacional, no período entre 2020 e 2022. A pandemia exacerbou desafios já encontrados pela comunidade internacional, como as restrições de mobilidade, assim como o acesso desigual a medicamentos e vacinas. Em certos contextos autoritários, as iniciativas de lockdown e distanciamento também foram mobilizadas para restringir as liberdades civis e de organização política. Certas respostas à pandemia também reforçaram o populismo com a adopção de um discurso negacionista, anti ciência e contrário a instituições multilaterais como a Organização Mundial de Saúde (OMS). O relacionamento entre o Brasil e o continente africano, no contexto da covid-19, precisa ser entendido a partir desses desafios e dos impactos que os mesmos deixaram na política internacional. No mesmo período, em Janeiro de 2022, o início do mandato brasileiro como membro nãopermanente do Conselho de Segurança das Nações Unidas (CSNU) também reforça os laços e interesses mútuos de cooperação entre o Brasil e o continente africano. Historicamente, a presença do Brasil no CSNU, principalmente no período do imediato pós-Guerra Fria, foi utilizada a favor dos países africanos parceiros, principalmente Angola e Moçambique. Em contrapartida, a maioria dos países africanos, em especial os países lusófonos, votam recorrentemente a favor das candidaturas brasileiras ao CSNU (Ministério das Relações Exteriores, 2021a). De forma a contribuir para uma melhor compreensão das dinâmicas apresentadas acima, o presente capítulo está dividido nas seguintes secções: uma análise geral sobre o acompanhamento da evolução da pandemia da covid no continente africano por parte dos diplomatas brasileiros, seguida de uma discussão sobre a cooperação brasileira no context da pandemia, e de uma secção sobre a covid-19 e as relações Brasil-Moçambique. O capítulo termina com a apresentação da conclusão. A pesquisa é beneficiada pelo acesso à documentação diplomática brasileira disponível via legislação brasileira de acesso à informação. Os documentos diplomáticos consultados incluem mensagens trocadas entre as diferentes embaixadas brasileiras, em especial a Embaixada do Brasil em Maputo-Brasemb Maputo, localizadas no continente africano e a Secretaria de Estado das Relações Exteriores (SERE), em Brasília.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; south-south cooperation / cooperação sul-sul

Classes of working women in Mozambique: an integrated framework to understand working lives - Stevano, Sara (Review of International Political Economy, 2022)
Feminist political economy has illuminated the gendered dimensions of the globalisation of production. Whilst this literature provides essential insights on gendered exploitation in export-oriented industries, women’s work in localised labour markets in the Global South remains underexplored. This paper seeks to address this gap by putting into dialogue three bodies of literature – feminist political economy of globalisation, political economy of development in southern Africa and the social reproduction of the everyday. It proposes an integrated conceptual framework to analyse women’s working lives and applies it to northern Mozambique. It makes two key findings. First, the lives of those working in localised labour markets are shaped by global capitalism through extreme fragmentation of labour regimes forcing people into multiple precarious forms of work – a process that entails the appropriation of women’s productive and reproductive labour. Second, the imperatives of social reproduction shape employment trajectories and expose differentiation among working women, seen for example through gendered constraints to mobility, care obligations and contributions to ceremonies. The implications are that the analysis of women’s working lives needs to capture three key aspects: social differentiation among working women, temporal and spatial dynamics of the everyday and the centrality of the reproduction of the social.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; gender / género; labour regimes / regimes de trabalho; social protection / proteção social; social reproduction / reprodução social

Monitoria comunitária independente ao PASD-PE COVID-19. Segunda Fase - Maputo e Namaacha - Plataforma da Sociedade Civil Moçambicana para a Protecção Social (PSC-PS) (Plataforma da Sociedade Civil Moçambicana para a Protecção Social (PSC-PS), 2021)
Os principais resultados da monitoria realizada em Montepuez destacaram a necessidade de: • Fortalecimento de mecanismos comunitários de participação e reforço do diálogo social entre comunidades e governo local; • Maior apropriação dos programas de protecção social básica por parte das comunidades e a necessidade de atribuir mais voz e protagonismo dos beneficiários sobre os serviços sociais prestados a nível destes programas; • Melhor comunicação e disseminação de informação estratégica sobre os programas de protecção social junto às comunidades, incluindo mais clareza sobre critérios de elegibilidade, valor dos benefícios, periodicidade e duração; • Maior mobilização social com vista a promover comunidades mais informadas e capacitadas para reivindicar os seus direitos sociais básicos; • Reforço de mecanismos de reclamações e queixas (clareza sobre como acessá-los); • Maior apoio para facilitação do acesso dos beneficiários aos pagamentos, em particular aqueles que precisam de auxílio para utilização dos telefones a partir dos quais recebem seus benefícios; • Ampliação dos métodos de pagamento para facilitar o acesso dos beneficiários às transferências.
Keywords: G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - COVID-19 / saúde – COVID-19; social protection / proteção social

The role of integrated community case management projects in strengthening health systems: case study analysis in Ethiopia, Malawi and Mozambique - Story, William T; Pritchard, Susannah; Hejna, Emily; Olivas, Elijah; Sarriot, Eric (Health Policy and Planning, 2021)
Integrated community case management (iCCM) has now been implemented at scale globally. Literature to-date has focused primarily on the effectiveness of iCCM and the systems conditions required to sustain iCCM. In this study, we sought to explore opportunities taken and lost for strengthening health systems through successive iCCM programmes. We employed a systematic, embedded, multiple case study design for three countries—Ethiopia, Malawi and Mozambique—where Save the Children implemented iCCM programmes between 2009 and 2017. We used textual analysis to code 62 project documents on nine categories of functions of health systems using NVivo 11.0. The document review was supplemented by four key informant interviews. This study makes important contributions to the theoretical understanding of the role of projects in health systems strengthening by not only documenting evidence of systems strengthening in multi-year iCCM projects, but also emphasizing important deﬁciencies in systems strengthening efforts. Projects operated on a spectrum, ranging from gap-ﬁlling interventions, to support, to actual strengthening. While there were natural limits to the inﬂuence of a project on the health system, all successive projects found constructive opportunities to try to strengthen systems. Alignment with the Ministry of Health was not always static and simple, and ministries themselves have shown pluralism in their perspectives and orientations. We conclude that systems strengthening remains ‘everybody’s business’ and places demands for realism and transparency on government and the development architecture. While mid-size projects have limited decision space, there is value in better deﬁning where systems strengthening contributions can actually be made. Furthermore, systems strengthening is not solely about macro-level changes, as operational and efﬁciency gains at meso and micro levels can have value to the system. Claims of ‘systems strengthening’ are, however, bounded within the quality of evaluation and learning investments.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; health / saúde

Provision and access to health services in Mozambique: An exploratory study on accountability and relations between health providers and users in Monapo district - Gonçalves, Euclides (POTENCIAR Programme, 2021)
This exploratory research set out to survey possible points of entry for POTENCIAR programme interventions and gather methodological insights for the ethnographic research component of the programme’s analytical strategy. It wil be used alongside other analytical studies undertaken by POTENCIAR (including the health sector analysis and the political economy analyses) to identify and design programme interventions. Following an inductive method, the team sought to assess the conditions and processes of health care provision and access from the perspective of health providers and residents in Monapo district in Nampula Province, northern Mozambique (POTENCIAR will implement its first PAI in Nampula province). To gain insights into accountability relations in the health sector, the team focused on the administrative and social institutions where health providers and users interact. The study asks the following question: From grounded perspectives of health providers and residents in Monapo district, what are the accountability issues in the provision and access to health services?
Keywords: *non-public; Ethnographic Studies; G - Mozambique / Moçambique; GD - Monapo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health / saúde

Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Who Can We Count On? Authority, Empowerment and Accountability in Mozambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (IDS Working Paper 546, Brighton: Institute of Development Studies, 2021)
In this paper, we explore the use of a governance diaries methodology to investigate poor households’ interactions with authority in fragile, conflict and violence-affected settings in Mozambique. The research questioned the meanings of empowerment and accountability from the point of view of poor and marginalised people, with the aim of understanding what both mean for them, and how that changes over time, based on their experiences with governance. The study also sought to record how poor and marginalised households view the multiple institutions that govern their lives; providing basic public goods and services, including health and security; and, in return, raise revenues to fund these services. The findings show that, even if the perceptions and, with them, the concepts of empowerment and accountability that emerged do not differ significantly from those identified in the literature, in terms of action and mobilisation there are distinctions. In our research sites we found that people rarely mobilise, even faced with prevalent injustices and poor basic service provision. Many claim to be ‘unable’ to influence or force ‘authorities’ to respond to their concerns and demands.
Accepted: 2021-02-02T10:30:54Z
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Actualidade Económica de Moçambique: Preparação para Recuperação (World Bank Group, 2021)
The global pandemic has taken a heavy toll on Mozambique’s economy. In 2020, the country experienced its first economic contraction in nearly three decades. COVID-19 (coronavirus) hit the economy as it was attempting to recover from the slowdown triggered by the hidden debt crisis and the tropical cyclones in 2019. Real gross domestic product (GDP) contracted by 1.3 percent in 2020, compared to a pre-Covid estimate of 4.3 percent, as external demand declined, domestic lockdown measures disrupted supply chains and depressed domestic demand, and liquified natural gas (LNG) investments were delayed. COVID-19 has caused a sudden income loss for enterprises and households, worsening living conditions, especially for the urban poor largely engaged in the informal sector. According to the National Institute of Statistics, as of June 2020, about 120,000 jobs were lost and 63,000 employment contracts suspended, with women being the most affected. Around 3 percent of the firms affected were forced to cease their activity. Services activities are the hardest hit. The tourism and hospitality industries have particularly suffered a steep decline in revenues. COVID-19 has jeopardized years of hard-won development gains, with about one million people estimated to have slipped into poverty in 2020 (as measured by the international poverty line of 1.90 US Dollars per day). While there is great uncertainty about the path of the pandemic, the economy is expected to gradually recover from 2021 as aggregate demand rebounds and LNG investments and extractive production gain momentum. Despite the expected recovery, the widespread deployment of COVID-19 vaccines will be at the core of a resilient recovery. This Economic Update explores the implications of COVID-19 for the economy, businesses and households. It makes recommendations for moving forward—in the short-term relief phase, as well as over the medium and longer term in order to 'build back better~!!.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde; private sector / setor privado

Mozambique Economic Update : Setting the Stage for Recovery (World Bank Group, 2021)
The global pandemic has taken a heavy toll on Mozambique’s economy. In 2020, the country experienced its first economic contraction in nearly three decades. COVID-19 (coronavirus) hit the economy as it was attempting to recover from the slowdown triggered by the hidden debt crisis and the tropical cyclones in 2019. Real gross domestic product (GDP) contracted by 1.3 percent in 2020, compared to a pre-Covid estimate of 4.3 percent, as external demand declined, domestic lockdown measures disrupted supply chains and depressed domestic demand, and liquified natural gas (LNG) investments were delayed. COVID-19 has caused a sudden income loss for enterprises and households, worsening living conditions, especially for the urban poor largely engaged in the informal sector. According to the National Institute of Statistics, as of June 2020, about 120,000 jobs were lost and 63,000 employment contracts suspended, with women being the most affected. Around 3 percent of the firms affected were forced to cease their activity. Services activities are the hardest hit. The tourism and hospitality industries have particularly suffered a steep decline in revenues. COVID-19 has jeopardized years of hard-won development gains, with about one million people estimated to have slipped into poverty in 2020 (as measured by the international poverty line of 1.90 US Dollars per day). While there is great uncertainty about the path of the pandemic, the economy is expected to gradually recover from 2021 as aggregate demand rebounds and LNG investments and extractive production gain momentum. Despite the expected recovery, the widespread deployment of COVID-19 vaccines will be at the core of a resilient recovery. This Economic Update explores the implications of COVID-19 for the economy, businesses and households. It makes recommendations for moving forward—in the short-term relief phase, as well as over the medium and longer term in order to 'build back better~!!.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde; private sector / setor privado

Análise da Proposta do Orçamento do Estado 2021 - Mussagy, Ibraimo H. (Observatório do Meio Rural, 2021)
A actual Proposta do Orçamento do Estado (POE) 2021 é a segunda para o quinquénio 2020-2024 e foi elaborada num contexto de transformações económicas e sociais impostas por um novo “normal” provocado pela pandemia da COVID-19, que resultou na maior recessão mundial estimada em cerca de -4.9% para 2020. Essa recessão foi causada pelas medidas de contenção que resultaram na paralisação da actividade económica em grande parte das economias. Em linha com as actuais tendências da economia mundial, a economia Moçambicana também tem registado uma desaceleração (parágrafo 2 da POE 2021). Este texto tem a finalidade de analisar a POE 2021, tendo em conta este contexto. Para tal, a análise foi feita com base nos seguintes documentos: Plano Económico e Social (PES) 2021, POE 2021, mapas integrantes¹, leis orçamentais anteriores e os Relatórios de Execução Orçamental (REO) recentes. Faz-se a articulação destes documentos para se poder perceber a evolução das componentes da POE 2021. O texto compreende três secções, nomeadamente a introdução, a análise do orçamento, onde, de forma específica, o texto analisa os pressupostos macroeconómicos subjacentes à proposta, a evolução das receitas e das despesas, faz uma discussão sobre o défice orçamental, destaca os orçamentos sectoriais com enfase para agricultura, onde o projecto SUSTENTA prevalece em grande parte da discussão, aborda a questão da descentralização e discute o endividamento público, e, na última secção, apresenta-se o resumo das constatações.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; budget / orçamento; decentralization / descentralização; education / educação; health / saúde

Relatório de Pesquisa Desigualdades e Resistência em Tempos de Pandemia: Impactos Da COVID-19 Nas Mulheres do Mercado Informal - Osório, Conceição; Loforte, Ana Maria; Vilanculo, Sérgio (WLSA Moçambique, 2021)
Este relatório de pesquisa buscou especificamente identificar no contexto mundial, regional e nacional as estratégias e as políticas públicas relativamente à situação das raparigas e mulheres, analisar as narrativas e discursos das organizações da sociedade civil e instituições de pesquisa, tanto as que têm como foco os direitos humanos, como as que definem como objecto a promoção da igualdade de género, e analisar o conteúdo dos media nacionais sobre a Covid-19, com destaque para as representações sobre violência de género. Para a realização da pesquisa foi importante a definição do grupo alvo, as mulheres que trabalham no informal, por serem das mais afectadas pela situação criada pela Covid-19, sendo muito pouco conhecidas as suas vozes, os seus problemas, necessidades e expectativas. A pesquisa foi enquadrada no Projecto “Mulheres e direitos humanos no contexto da COVID-19 em Moçambique” e surgiu no âmbito de uma parceria entre a WLSA Moçambique com as Aliadas e o CESC, procurando conhecer melhor como é que, em situação de pandemia, se configuravam os direitos humanos das mulheres, considerando as desigualdades estruturais e as relações desiguais de poder.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; informality / informalidade

Navigating Civic Space in a Time of COVID-19: The Case of Mozambique - Pereira, Crescêncio; Forquilha, Salvador; Shankland, Alex (Institute for Social and Economic Studies, 2021)
This report builds on the Action for Empowerment and Accountability (A4EA) research project Navigating Civic Space, which seeks to analyze the extent to which COVID-19 is contributing to the opening or closing of space for civic action in three countries, namely Mozambique, Nigeria and Pakistan. Focusing on Mozambique, the report uses theoretical and methodological tools produced by the work stream and is essentially structured around the three main research questions: What is known about the civic space trend in Mozambique before the arrival of the COVID-19 pandemic?; How are different actors responding to the COVID-19 pandemic affecting the civic space in Mozambique?; What are the medium and long term implications for governance in Mozambique?
Accepted: 2021-04-28T09:57:56Z
Keywords: G - Mozambique / Moçambique; L - english / inglês; civic space / espaço cívico; health - COVID-19 / saúde – COVID-19

African Economic Outlook 2021: From Debt Resolution to Growth: The Road Ahead for Africa - African Development Bank (African Development Bank, 2021)
The 2021 edition of the African Economic Outlook focuses on debt resolution, governance, and growth in Africa. Chapter 1 examines Africa’s growth performance and outlook amid the COVID–19 pandemic. The chapter emphasizes policy options to mitigate the effects of the pandemic in the short, medium, and long terms. Chapter 2 explores the causes and consequences of Africa’s debt dynamics by showing how the changing structure and composition of debt create vulnerabilities. In chapter 3, the report takes stock of the challenges in the current global architecture for debt resolution and explores the link between governance and growth with an emphasis on proposed reforms to improve the processes of debt resolution, governance, and sustainable growth
Publisher: African Development Bank Group 978-9973-9854-5-3 (electronic)
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; governance / governação; health - COVID-19 / saúde – COVID-19

A COVID-19 e suas implicações na governação municipal em Moçambique: um estudo de caso a partir do município de Gondola - António, Bernardino (Desafios para Moçambique 2021, 2021)
Tomando como exemplo o município de Gondola, na província de Manica, este artigo analisa as implicações da COVID-19 na governação municipal, destacando a interacção entre a edilidade e os munícipes no desenvolvimento do mesmo. O texto defende o argumento segundo o qual, apesar de a COVID-19 ter impactado negativamente nas lógicas do Governo de Gondola, a pandemia, por si só, não constitui factor explicativo para a fraca interacção entre as autoridades e os munícipes, pois os baixos níveis de interacção entre os Vereadores e os cidadãos constitui um problema de carácter estrutural, que caracteriza o Governo não só ao nível das autarquias, mas também a outros níveis de governação em Moçambique. O artigo está organizado em três secções, além da introdução. Na primeira secção, faz se uma breve caracterização do município de Gondola, mostrando o contexto da análise aqui feita. Na segunda secção, aborda-se o papel dos municípios na gestão da COVID-19 em Moçambique. Na terceira secção, descreve-se a COVID-19 e as suas implicações no Governo de Gondola, destacando a questão da interacção entre as autoridades municipais e os munícipes. O artigo resulta de uma pesquisa realizada no município de Gondola em 20206, no âmbito do projecto de pesquisa «Barómetro da Governação Municipal», em curso no Instituto de Estudos Sociais e Económicos (IESE) desde 2017. A pesquisa baseou-se numa metodologia qualitativa, com recurso a entrevistas semiestruturadas, discussões em grupos focais e observação no terreno, realizadas em 10 bairros do município de Gondola, nomeadamente Mazicuera, Mucessua, Josina Machel, Bengo, Nhachoco, Eduardo Mondlane, 3 de Fevereiro, 7 de Abril, Francisco Manyanga e 25 de Junho. Foram realizadas quatro discussões em grupos focais e nove entrevistas semiestruturadas com moradores, membros do Governo Municipal (Presidente e Vereadores), membros da Assembleia Municipal, líderes comunitários, comerciantes locais e organizações da sociedade civil. A pesquisa de campo decorreu ao longo de 15 dias, entre Novembro e Dezembro de 2020
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; governance / governação; health - COVID-19 / saúde – COVID-19; politics / política

«Se alguém está cansado de viver» A economia informal e a segurança social - Castel-Branco, Ruth (Desafios para Moçambique 2021, 2021)
A fraca resposta do Estado aos impactos socioecónomicos da pandemia da COVID-19 salientou a necessidade de reformular o sistema da Segurança Social em Moçambique; de evoluir de um paradigma social trabalhista para um paradigma que reconhece a centralidade da economia informal e a responsabilidade redistributiva do Estado, assente num contrato social. Não existe uma única abordagem para a inclusão dos trabalhadores informais na protecção social. A economia informal é extremamente diversificada e estratificada por tipo de atividade, formas de organização e estruturas de rendimento. Portanto, é necessário considerar abordagens diferenciadas que respondem às várias realidades dos trabalhadores informais, incluindo a ausência de um empregador e a irregularidade dos rendimentos. As medidas de Segurança Social Não-Contributiva introduzidas durante a pandemia podem servir com base para um sistema redistributivo mais robusto. Mas no reforço do papel redistributivo do Estado, é importante não absolver os empregadores da sua responsabilidade de reprodução social. Por exemplo, o Regulamento de Trabalho Doméstico estipula que, por motivos do Instituto Nacional de Segurança Social, os trabalhadores domésticos devem ser considerados trabalhadores por conta própria (RdM, 2008). Porém, segundo a Lei de Trabalho (RdM, 2007b), os trabalhadores por conta própria são aqueles que: podem escolher os processos e meios de trabalho, sendo estes da sua propriedade, no todo ou em parte; não estão sujeitos a horários de trabalho, salvo se os mesmos resultarem da lei ou regulamentos; não se integram na estrutura produtiva ou cadeia hierárquica de uma única empresa, nem constituem elemento essencial ao desenvolvimento dos objectivos de qualquer entidade empregadora; e podem fazer-se substituir livremente. Esta inconsistência reflecte o poder negocial da classe empregadora na definição do Regulamento. Apesar de não serem trabalhadores informais, os trabalhadores domésticos são informalizados pela falta de protecções laborais e sociais adequadas e a sua devida aplicação. Portanto, é crítico garantir que medidas orientadas à expansão da Segurança Social – seja a Segurança Social Contributiva ou Não-Contributiva – estejam articuladas com medidas para reforçar os direitos laborais num contexto de fraca fiscalização, informalização e informalidade generalizada.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social security / segurança social; health - COVID-19 / saúde – COVID-19; informality / informalidade; society / sociedade

Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

Política económica em contexto de pandemia: uma reflexão em trono das medidas de mitigação dos efeitos da COVID-19 sobre a economia de Moçambique - Muianga, Carlos; Ibraimo, Yasfir (Desafios para Moçambique 2021, 2021)
Este artigo pretende reflectir sobre as medidas para mitigação dos efeitos da COVID-19 na economia de Moçambique e as suas implicações analíticas. Diferentemente de estudos anteriores sobre os impactos da pandemia e das medidas de mitigação adoptadas pelo Governo de Moçambique (Mapisse et al., 2021), este artigo parte da análise da estrutura da economia e do seu padrão de acumulação nas últimas duas décadas, na tentativa de melhor questionar a eficácia destas medidas. O artigo argumenta que, à semelhança das crises cíclicas pelas quais a economia de Moçambique passou nas últimas décadas (Castel-Branco and Ossemane, 2010; Castel-Branco, 2017), a crise provocada pela COVID-19 expõe e exacerba as fragilidades e vulnerabilidades do padrão de crescimento e a sua limitada capacidade em resolver questões centrais de transformação social e económica. Dadas as fragilidades e vulnerabilidades associadas ao padrão de crescimento económico e ao «modelo» de política económica, as medidas de mitigação dos efeitos da pandemia sobre a economia são limitadas relativamente à complexidade dos impactos socioeconómicos da COVID-19. Mais do que a sua limitada capacidade para relançar a actividade produtiva, dada a estrutura da economia, as mesmas são insuficientes para lidar com os impactos mais severos da pandemia, sobretudo para os grupos sociais mais vulneráveis. Entretanto, a COVID-19 tem chamado a atenção à necessidade de acção política e mudança «radical» na prossecução da política económica, incluindo o papel do Estado na economia (Stevano et al., 2021). Contudo, as principais medidas de política económica até então adoptadas continuam a seguir um «modelo» que, há décadas, se tem mostrado ineficaz em resolver, a médio e longo prazo, as questões de transformação económica e social do País. Este artigo está organizado em quatro secções, incluindo a introdução. A segunda faz uma breve descrição e análise da estrutura da economia e do padrão de crescimento económico em Moçambique, nas últimas duas décadas. O objectivo desta secção é fornecer uma base analítica que ajude a interrogar as medidas de mitigação dos efeitos da COVID-19 sobre a economia, enquanto, ao mesmo tempo, ajuda a explicar o tipo de economia que a pandemia encontrou, as suas características fundamentais e o seu funcionamento. A terceira secção descreve as principais medidas adoptadas pelo BM e pelo Governo para mitigar os efeitos da COVID-19, questionando-as em função da estrutura da economia e do quadro de implementação de política monetária e fiscal e as suas contradições e tensões. A quarta secção conclui e avança algumas questões para reflexão.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; government policy / politica governamental; health - COVID-19 / saúde – COVID-19

Navengando o espaço cívico em contexto da pandemia da COVID-19: o caso de Moçambique - Pereira, Crescêncio; Forquilha, Salvador; Shankland, Alex (Desafios para Moçambique 2021, 2021)
Este artigo circunscreve-se no âmbito do projecto de pesquisa Navigating Civic Space in a Time of Covid-19 (Navegando o Espaço Cívico em Tempo da Covid-19), que procurou analisar em que medida o coronavírus estava a contribuir para a abertura ou o fechamento do espaço para a acção cívica em três países, nomeadamente Moçambique, Nigéria e Paquistão. Com enfoque em Moçambique, este artigo serve-se de ferramentas teóricometodológicas produzidas pela equipa de pesquisa dos três países acima mencionados e estrutura-se essencialmente em torno das três principais questões da pesquisa: · O que se sabe sobre a tendência do espaço cívico em Moçambique antes da chegada da pandemia da COVID-19? · Como é que diferentes actores estão a responder à pandemia da COVID-19 e de que maneira estas respostas vêm a afectar o espaço cívico em Moçambique? · Quais são as implicações de médio e longo prazo para a governação em Moçambique? O material usado para a elaboração do artigo foi produzido com base numa abordagem metodológica que combina quatro componentes, nomeadamente a) avaliação de base sobre a natureza do espaço cívico em Moçambique antes da pandemia da COVID-19; b) painel virtual de observação, constituído por especialistas moçambicanos da sociedade civil, com reuniões mensais; c) análise de meios de comunicação social com recurso a catálogos de eventos; d) entrevistas com uma selecção de informantes-chave para complementar a informação produzida pelas outras componentes. Neste contexto, foi elaborado um relatório de avaliação de base (Pereira, C. & Forquilha, 2020) e foram realizadas seis sessões de painéis virtuais de observação. Com temas previamente acordados, as sessões mensais tinham a duração de duas horas e os assuntos nelas discutidos eram gravados, registados e transformados em relatórios mensais que, posteriormente, eram discutidos em encontros mensais internacionais, envolvendo equipas de pesquisa do IDS, IESE e os parceiros de pesquisa da Nigéria e do Paquistão.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civic space / espaço cívico; health - COVID-19 / saúde – COVID-19; politics / política

A COVID-19 e as vacinas em Moçambique: algumas notas para reflexão a partir da teoria <sociedade de risco> - Posse, Lúcio (Desafios para Moçambique 2021, 2021)
No presente texto, procuro, por meio da teoria «Sociedade de Risco», elaborada por Ulrich Beck (2011 [1986]), reflectir sobre como os «moçambicanos» elaboram os seus significados e sentidos de risco em relação à COVID-19 e à vacina, e como estes têm estado a desenvolver os seus comportamentos na resposta à pandemia e à vacina. Em termos pragmáticos, procuro chamar a atenção para a necessidade da compreensão dos riscos, como forma de tentar fazer com que as respostas, não só à COVID-19, mas também a outros fenómenos, não fiquem reféns das percepções dos riscos, ao ponto de as comprometer – no sentido de ignorar ou exagerar –, porque, como refere (Beck, 2002:4), «o maior perigo não é o risco [em si], mas a percepção [que as sociedades podem desenvolver] do risco [ao ponto dos seus comportamentos se tornarem num obstáculo para a resolução dos problemas]». Com este texto, mostro que a percepção – à semelhança de outros contextos – que a sociedade moçambicana tem da COVID-19 e da vacina são produto da «racionalidade social do risco», na medida em que os seus sentidos e significados são determinados por questões socioeconómicas, culturais (particularmente os hábitos alimentares), raciais, climáticas, políticas e por experiências: (i) da colonização no uso da medicina para dominar e fazer experimentos clínicos nos africanos, e (ii) da falta de tratamento e da incapacidade dos sistemas de saúde darem resposta ao vírus e aos efeitos colaterais das vacinas, que por vezes causam a morte. Ademais, estas percepções têm estado a estruturar o comportamento dos moçambicanos, primeiro, no que se refere à doença, ao manifestarem, de um lado, a indiferença e/ou despreocupação por considerarem que a doença é dos «outros» e, do outro, pela tomada de medidas de prevenção, num claro sinal de pânico e; segundo, quanto à vacina ao manifestarem, de um lado, a desconfiança em relação à origem, segurança e objectivos da vacina e, do outro, ao receberem a vacina por acreditarem que, em termos de riscos/ benefícios, há muito mais benefícios em receber a vacina.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; politics / política

A recessão económica em Moçambique: foi a COVID-19? Um olhar a partir do sector externo - Sambo, Michael Godet (Desafios para Moçambique 2021, 2021)
Este artigo argumenta que a crise económica em Moçambique não resulta da eclosão da pandemia em si, e dos seus efeitos directos na economia moçambicana, mas sim, que a pandemia exacerbou uma crise pré-existente. O artigo resulta de análise bibliográfica e documental, com ênfase para a análise de dados estatísticos de múltiplas fontes internacionais e nacionais, destacando as fontes oficiais, e analisa as dinâmicas económicas no contexto da COVID-19, com enfoque nas relações económicas de Moçambique com o resto do Mundo desde antes da eclosão da pandemia até aos princípios de 2021. Além da introdução, este artigo é desenvolvido em duas secções seguidas da conclusão. A primeira secção analisa as dinâmicas das políticas públicas no contexto da dependência externa, e a segunda investiga as dinâmicas da economia de Moçambique em relação ao resto do mundo, analisando os antecedentes e as variações no âmbito da COVID-19, com vista a aferir a sua relação; segue-se finalmente uma conclusão e implicações da análise.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19

Lições da COVID-19 sobre o papel da poupança doméstica: O que dizer de Moçambique? - Siúta, Moisés (Desafios para Moçambique 2021, 2021)
O presente artigo procura discutir lições que se podem tirar em relação ao papel da poupança para Moçambique, no âmbito da pandemia da COVID-19. O artigo inspira-se na pesquisa sobre poupança, pobreza e protecção social desenvolvida pelo Instituto de Estudos Sociais e Económicos (IESE), que estabelece a ligação entre poupança e protecção social, tendo em vista estudar mecanismos que permitam desenvolver um sistema de protecção social financeiramente viável em Moçambique (Siúta, 2019b). O objectivo deste artigo é estabelecer a ligação entre a poupança e a COVID-19, discutindo o seu papel no âmbito da resposta à pandemia. A metodologia usada, além da revisão de literatura, inclui a exploração de dados sobre a evolução da pandemia em diversos países, fornecidos pela Organização Mundial da Saúde (OMS/WHO (World Health Organization)), cuja base de dados foi preparada e disponibilizada publicamente por Ritchie et al. (2020). Para completar a análise através da exploração de dados sobre a economia dos países, analisando, principalmente, a evolução da poupança doméstica e do produto dos países, recorreu-se à base de dados dos indicadores de desenvolvimento dos países, disponibilizada pelo Banco Mundial (World Bank, 2021). O artigo, incluindo a presente introdução, subdivide-se em quatro secções. Nas secções a seguir, na primeira, discute-se a relevância da poupança doméstica, no contexto da pandemia da COVID-19, com base numa abordagem teórica da poupança; a segunda secção, baseada em dados sobre a poupança doméstica e a capacidade de testagem e vacinação contra a COVID-19, procura discutir a relevância da poupança doméstica nos países ao redor do Mundo, incluindo o caso de Moçambique. Na última secção, apresenta-se uma breve discussão sobre o contexto moçambicano e a relevância da poupança doméstica.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; poverty / pobreza; social protection / proteção social; society / sociedade

Acção Social em contexto de COVID-19: Respostas e desafios em Moçambique - Siúta, Moisés; Félix, Matusse (Desafios para Moçambique, 2021, 2021)
O presente artigo tem como objectivo partilhar as medidas de resposta em contexto da COVID-19 implementadas pelo INAS, no âmbito dos programas do Governo para assistência social, tendo em conta que a eclosão da pandemia constituiu mais um factor a colocar o subsistema nacional da Segurança Social Básica (SSB) sob pressão, a fim de dar resposta a um grupo cada vez mais crescente de cidadãos moçambicanos em situação de extrema pobreza e de vulnerabilidade. O artigo está divido em cinco secções, incluindo esta introdução. São abordados os seguintes assuntos: segunda secção, a dimensão da COVID-19 e a relevância da assistência social; terceira, resposta à pandemia no âmbito dos programas do INAS; quarta, os principais desafios da acção social na resposta à pandemia; e a quinta secção apresenta considerações finais e possíveis lições
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - COVID-19 / saúde – COVID-19; social action / ação social; social protection / proteção social

Essencial para quê? Uma visão global de reprodução social sobre a reorganização do trabalho durante a pandemia da COVID-19 - Stevano, Sara; Ali, Rosimina; Jamieson, Merle (Desafios para Moçambique 2021, 2021)
O presente artigo pretende investigar a noção de trabalho essencial através de uma lente feminista global centrada na reprodução social. Abordam-se duas questões principais: primeiro, o que é trabalho essencial e como é que esta terminologia tem sido utilizada em diferentes países do Sul e do Norte Global. Através de uma revisão da literatura, decretos, documentos orientadores e artigos de jornal, procedemos ao mapeamento dos significados de trabalho essencial em todo o Mundo, utilizando como exemplos África do Sul, Brasil, Canadá, Inglaterra, Índia, Itália e Moçambique. Em segundo lugar, tomando como ponto de partida a afirmação feita pelos teóricos da reprodução social de que o reconhecimento de formas de trabalho desvalorizadas como essenciais constitui uma via para revalorizar o trabalho socialmente reprodutivo (Bhattacharya, 2020; Stevano et al., 2021), perguntamos se este potencial foi explorado até agora e, caso contrário, que limitações, omissões e contradições o estão a impedir. A perspectiva global é complementada por um «foco» sobre Moçambique como um país de baixa renda, localizado no Sul Global, ocupando uma posição periférica nas economias globais e regionais e com uma grande percentagem de trabalhadores vulneráveis e essenciais. As ilustrações de Moçambique baseiam-se na investigação preliminar sobre o trabalho nas agro-indústrias, realizado pelas autoras antes da pandemia, em combinação com a revisão de artigos de jornal, documentos orientadores, observações e evidência primária seleccionada durante a pandemia
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; employment / emprego; health - COVID-19 / saúde – COVID-19; social reproduction / reprodução social

Qualidade da assistência pré-natal em Nampula, Moçambique - Muleva, Belarmina Reis (Universidade de São Paulo, 2020)
A realização da consulta pré-natal de alta qualidade está diretamente relacionada aos melhores indicadores maternos e fetais e à prevenção de morbimortalidade materna. Em Moçambique, estudos sobre assistência pré-natal mostram que a maior parte das mulheres fez pré-natal, mas apenas metade fez as quatro ou mais consultas preconizadas pelo Ministério da Saúde. Além disso, as gestantes têm se apresentado aos centros de saúde para fazerem sua primeira consulta pré-natal somente no final do segundo trimestre da gestação. Essas questões mostram que a qualidade da assistência ao pré-natal é ainda um desafio, embora haja poucos estudos sobre o tema naquele contexto. Objetivo: Avaliar a qualidade da assistência pré-natal entre as mulheres do município de Nampula, em Moçambique. Método: Trata-se de um estudo quantitativo, do tipo transversal, realizado no município de Nampula, em Moçambique, na África. A amostra constou de 393 mulheres de 18 a 49 anos, com parto ocorrido em maternidade ou no domicílio no segundo semestre de 2019. As entrevistas foram conduzidas por meio de instrumento estruturado, aplicado face-a-face, até 15 dias após o parto. A qualidade da assistência pré-natal foi analisada com base nas diretrizes do Ministério da Saúde de Moçambique. A qualidade do pré-natal foi categorizada em inadequada e adequada. Modelos de regressão logística múltipla foram conduzidos para analisar os aspectos associados a ter realizado pré-natal adequado. Resultados: As mulheres participantes do estudo tinham, em média, 26 anos de idade, e metade tinha ensino primário (52,4%). Embora todas as mulheres tenham realizado o pré-natal, apenas 13,0% tiveram o pré-natal classificado como adequado. Mulheres que realizaram pré-natal em gestações anteriores (OR=4,28; IC95%=1,45-12,62) e com gravidez planejada (OR=2,51; IC95%=1,11-5,68) foram as que tiveram mais chance de ter um pré-natal adequado. Observou-se que a assistência pré-natal não atendeu ao que é preconizado, como a idade gestacional de início do pré-natal, número mínimo de consultas a serem feitas, realização de alguns exames (hemograma, glicemia, tipagem sanguínea e fator Rh) e oferta de orientações sobre sinais de risco e de parto. Quanto à satisfação com a assistência pré-natal recebida, mais da metade das mulheres mostrou-se insatisfeita com o tempo de espera para ser atendida pela profissional de saúde. Conclusão: De modo geral, os critérios preconizados para que uma assistência ao pré-natal seja de alta qualidade não estão incorporados na prática clínica no município de Nampula.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health - maternal and child / saúde - materno-infantil; health / saúde

Covid-19: Organizações questionam gastos do Governo moçambicano | DW | 11.08.2020 - Deutsche Welle (DW.COM, 2020)
Em Moçambique, a sociedade civil aponta falta de transparência e pede esclarecimentos ao Governo sobre os 14 mil contratos sem concurso público e os 68 mil milhões de meticais gastos durante o estado de emergência.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; health - COVID-19 / saúde – COVID-19; health / saúde; transparency / transparência

First confirmed occurrence of the yellow fever virus and dengue virus vector Aedes (Stegomyia) luteocephalus (Newstead, 1907) in Mozambique - Abílio, Ana Paula; Kampango, Ayubo; Armando, Eliseu J.; Gudo, Eduardo S.; das Neves, Luís C. B.; Parreira, Ricardo; Sidat, Mohsin; Fafetine, José M.; de Almeida, António Paulo G. (Parasites & Vectors, 2020)
Mozambique, same as many other tropical countries, is at high risk of arthropod-borne virus (arbovirus) diseases and recently two dengue virus (DENV) outbreaks occurred in the northern part of the country. The occurrence of some important vector species, such as Aedes (Stegomyia) aegypti (Linnaeus) and Ae. (Stg.) albopictus (Skuse), besides several other sylvatic vectors, have been reported in the country, which may indicate that the transmission of some arboviruses of public health importance may involve multiple-vector systems. Therefore, knowing the occurrence and distribution of existing and the new important vectors species, is crucial for devising systematic transmission surveillance and vector control approaches. The aim of this study was to map the occurrence and distribution of mosquito species with potential for transmitting arboviruses of human and veterinary relevance in Niassa Province, Northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lago; GP - Niassa; L - english / inglês; health / saúde

Health, development, and institutional factors: The Mozambique case - Garrido, Paulo Ivo (2020)
Abstract: The central aim of this text is to show the impact institutions have on the performance of the health sector in Mozambique. The text shows that of the social determinants of health, institutions play a central role in the performance of the Mozambican health sector—and, through it, economic and social development—particularly for the poorer and more vulnerable, such as children, women, the disabled, and the elderly. It is also argued that the deficiencies and inefficiencies of the operation of the health sector in Mozambique are largely the result of the fact that the institutions with influence on the health sector are controlled by a minority of privileged people who do not give the appropriate priority to the basic health needs of the majority of the population. Finally, it is argued that the most important institutional measures for improving the state of health of Mozambicans are the revision of the Constitution of the Republic, the strengthening of the National Health System (particularly the National Health Service), and the reduction of poverty and economic and social inequality.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Saúde, desenvolvimento e factores institucionais: o caso de Moçambique - Garrido, Paulo Ivo (2020)
Este texto tem por objectivo central mostrar o impacto que as instituições têm no desempenho do sector da Saúde em Moçambique. No texto demonstra-se que, de entre os Determinantes Sociais da Saúde, as instituições têm um papel central no desempenho do sector da Saúde — e, por seu intermédio, no desenvolvimento económico e social — dos moçambicanos, em especial dos mais pobres e mais vulneráveis, como as crianças, as mulheres, as pessoas com deficiência e os idosos. Argumenta-se também que as deficiências e ineficiências do funcionamento do sector da Saúde em Moçambique resultam em larga medida do facto de as instituições com influência no sector da Saúde serem controladas por uma minoria de privilegiados que não dá a prioridade devida às necessidades básicas em saúde da maioria da população. Finalmente, argumenta-se que as medidas de carácter institucional mais importantes para a melhoria do estado de saúde dos moçambicanos são a revisão da Constituição da República, o reforço do Sistema Nacional de Saúde (em particular do Serviço Nacional de Saúde) e a redução da pobreza e das iniquidades económica e social.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Unpacking the Potential Socioeconomic Impact of the Coronavirus Pandemic in Mozambique: A United Nations Situation Analysis and Policy Recommendations - United Nations Mozambique (United Nations, 2020)
The Coronavirus pandemic arrives in Mozambique at a time when, after several years of modest economic performance, the Mozambican economy was starting to show signs of recovery. Hence, the latest projections of the IMF of November 2019 had the Mozambican economy growing at 6% in 2020, with medium term projections reaching 9% and above after 2023, following the initiation of LNG exploration operations in the north of the country. Despite this improving macroeconomic outlook prior to the outbreak of the Coronavirus pandemic, living conditions for many Mozambicans remain harsh. Poverty afflicts almost half of the population, 46.1% according to the 2014/15 national household survey, and many people continue without access to basic services, with the proportion of Mozambicans with access to basic water supply, basic sanitation and electricity remaining at very low levels: 55.7%, 29.4% and 27.4% in 2017, respectively. Moreover, despite improvements in healthcare conditions, Mozambicans, especially women and children, continue to be severely afflicted by disease and sickness. In general, living conditions tend to be worse in rural than in urban parts of the country. The coronavirus pandemic is almost certainly going to change this short- and medium-term economic outlook and could potentially have a very significant socioeconomic impact in Mozambique. However, while all available evidence points in this direction, at this stage it is difficult to ascertain and quantify the extent of this impact, given the speed at which things are changing around the world and the uncertainly surrounding the epidemiological profile of the Coronavirus, which makes it hard to assess how long the containment and lockdown measures being applied around the world will need to remain in place. While a detailed quantification of the socioeconomic impact of the coronavirus pandemic may not be feasible, it is still useful to identify possible transmission channels through which the pandemic may affect the Mozambican economy and society. It is also useful to identify key issues that are likely shape shortand medium-term socioeconomic prospects in Mozambique as a result of the Coronavirus pandemic outbreak in Mozambique. The following sections outline some of these.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde

Baseline Assessment of Facility and District Capacity: Alcançar Qualidade de Serviços de Saúde para Mulheres e Crianças - USAID; fhi360; Alcançar (FHI 360, 2020)
The Alcançar Baseline Assessment of Facility and District Capacity was conducted to establish an evidence base against which to measure project performance and impact over the life of the project and to inform project priorities and planning. The assessment includes a census of health centers and hospitals in Nampula province - the population of facilities that the project is expected to influence. Trained data collection teams interviewed facility and district staff to collect current information on (1) facility infrastructure and policies, (2) human resources, (3) ordering and management of maternal and child health (MCH) commodities, (4) provision of MCH services (5) knowledge of MCH care components, and (6) emergency referral capacity. Additionally, they reviewed and extracted data from facility registers over a 6-month period and observed antenatal care (ANC) consultations. Data collectors visited each of the district health offices (Serviço Distrital de Saúde, Género, Criança e Acção Social, SDSMAS) to gather information on district health capacity to provide clinical mentoring, implement quality improvement and death audits, and manage commodities. This assessment report presents selected results.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; health - maternal and child / saúde - materno-infantil; health / saúde

A segurança social em Moçambique: conversa para o boi dormir ou um instrumento de redistribuição viável? - Castel-Branco, Ruth Kélia (Desafios para Moçambique 2020, 2020)
Nas últimas décadas, houve uma ressurgência de interesse na Segurança Social como instrumento redistributivo capaz de reduzir a pobreza e a desigualdade e promover o crescimento económico inclusivo. Este crescente interesse a nível global deve-se ao reconhecimento de que o desenvolvimento social não resulta inevitavelmente do crescimento económico, e, aliás, pode ser bem o contrário: que formas de Segurança Social vinculadas ao emprego formal são inadequadas dada a informalidade generalizada e que transferências monetárias não contributivas são possíveis mesmo em países em vias desenvolvimento como Moçambique (Mkandawire, 2011). Nas duas décadas anteriores à crise da Ematum, Moçambique registou um índice de crescimento médio de 7,5 % do PIB. Porém, impulsionado por uma indústria extractiva intensiva em capital, este não resultou em melhores condições de vida para a maioria dos moçambicanos. A Crise da Ematum piorou a situação. Segundo simulações da UNU-WIDER, a crise resultou no aumento do índice da pobreza de 46,1 % em 2014, e de aproximadamente 60 % em 2016 (Mambo et al., 2018). Alarmado pela situação, o antigo Ministro de Administração Estatal, Óscar Monteiro, sugeriu, durante a reunião do Comité Central da Frelimo em Maio de 2019, a rápida expansão do sistema de Segurança Social em Moçambique, mas o Governo optou por não a fazer: "A gravidade da situação requer medidas urgentes. E eu digo isto não porque não é apenas uma questão eleitoral, mas é uma questão de humanidade... Porque é que nós não começamos a distribuir dinheiro, usando a rede existente, ampliando, melhorando... Esse dinheiro não se vai perder... Esse dinheiro vai aumentar o consumo, vai encorajar a produção, vai financiar a recuperação. (Monteiro, 2019)" A crise da Covid expôs mais uma vez a fragilidade do nosso modelo de desenvolvimento económico, e a fraqueza dos mecanismos de redistribuição existentes. Projecções da UNU-WIDER concluíram que apenas 7 % dos moçambicanos tinham as condições para sobreviver a um lockdown total (Jones, Egger & Santos, 2020). O Governo acabou por optar por um lockdown parcial, permitindo que várias instituições públicas e privadas continuassem abertas. No entanto, a questão da expansão da Segurança Social continua oportuna não só como medida de resposta de emergência durante a crise da Covid, mas também como instrumento redistributivo com a capacidade de promover o desenvolvimento inclusivo. Este artigo começa por uma análise do actual sistema de Segurança Social, seguida por uma discussão das medidas de emergência que foram propostas, as sugestões rumo a um sistema de Segurança Social universal, e os riscos – principalmente o risco da financeirização da Segurança Social com a terceirização dos sistemas de registo e pagamentos. O artigo é concluído com uma discussão do tipo de mobilização que será necessário para garantir a expansão adequada da Segurança Social. Como disse o abolicionista Frederick Douglass, «sem luta não há progresso... O poder não concede nada sem demanda. Nunca concedeu e nunca concederá» (Frederick, 1851).
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social security / segurança social; health - COVID-19 / saúde – COVID-19; social protection / proteção social

Pânico e Medo: Desafios Dos Media Moçambicanos na Cobertura da COVID-19 - Joanguete, Celestino (Desafios para Moçambique 2020, 2020)
O principal foco do estudo são os diferentes enquadramentos da tonalidade discursiva adoptada pelos media nas suas narrativas sobre o novo coronavírus. Nesta perspectiva, a principal concentração como objecto de estudo são a rádio, a televisão, o jornal e as redes sociais da Internet. Neste último medium, escolhemos analisar especificamente as narrativas do Facebook e WhatsApp por serem as redes sociais mais populares em Moçambique. Socorremo-nos de duas metodologias de estudo bastante presentes no campo das ciências sociais, a análise de conteúdo desenvolvida por Bardin (2006) e a de observação sistemática. Foi fundamental adoptar estes métodos pela vantagem de permitirem recolher dados no momento da ocorrência dos factos, sem criar situações artificiais, e avaliar alguns aspectos para os quais não há outras técnicas de recolha de evidências. Uma análise sobre os diversos atributos descritivos do coronavírus permitiu compreender a construção do discurso mediático e a sua influência social. A análise de conteúdo das narrativas dos media moçambicanos facilitou a compreensão dos elementos constitutivos de textos jornalísticos, nas produções discursivas dos quais os termos, os adjectivos, as imagens, as descrições, o foco e as temáticas desempenham o papel fundamental.
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; health / saúde

Análise do Plano Económico e Social e Orçamento do Estado de 2020 nas Áreas da Saúde, Água e Saneamento - Marrengula, Constantino (Forum de Monitoria do Orçamento, FMO Mais, PAANE, 2020)
Os objectivos e os pilares do PES e OE de 2020 não mudaram, substancialmente, em comparação com o que foram as prioridades do quinquênio 2015-2019. Em linha com os compromissos internacionais, o Governo procurou manter os pesos relativos da despesa nos sectores prioritários, com particular realce para a educação e a saúde. Contudo, o aumento dos preços e dos encargos da dívida, que se seguiu à descoberta das dívidas não declaradas, baixou o valor real das provisões feitas nestes sectores. O valor de cerca de 26 mil milhões de Meticais reservado para a saúde em 2020 representa uma redução em relação ao que tinha sido programado para 2019, não obstante os desafios impostos pela pandemia da Covid19. A redução em termos reais do orçamento da saúde, ocorre num quadro geral, em que todas as metas previstas para o quinquênio passado foram revistas em baixa, ou não foram cumpridas. Por exemplo, num ano eleitoral como foi 2019, a taxa de realização da meta de recrutamento de profissionais para o sistema nacional da saúde situou-se em volta de 50%. As metas do PES e OE 2020 da saúde não parecem suficientes para que o sector recupere dos incumprimentos do quinquênio passado, num contexto que conta com a pandemia da Covid-19. Para o sector de água e saneamento, os acordos assinados com o Exim Bank da Índia, o Banco Mundial, e a SADC deram um novo impulso ao Programa PRAVIDA, mas o nível de realização das metas do PES e do orçamento do sector não foi substancialmente diferente do que aconteceu na saúde. Quando o orçamento aumentou em 2019 a taxa de execução do orçamento baixou para 32%, com incumprimentos em intervenções com impacto directo na pobreza, tanto rural como na zona peri-urbana. A revisão em baixa das metas do PES de 2020, em comparação com o definido para 2019, alarga o tempo necessário para que a intervenção do Estado no sector faça a diferença no acesso à água e saneamento. Num cenário de crescimento populacional, quanto mais conservadora e lenta for a intervenção maior é o atraso na correcção dos problemas identificados, o que certamente tem implicações na materialização dos objetivos de desenvolvimento sustentável. Reverter o cenário que sustenta as taxas de execução sub-óptimas dos orçamentos aprovados e a queda em termos reais das disponibilidades nos sectores prioritários constitui o principal desafio das Finanças Públicas em Moçambique. Embora não esteja claro o que poderá ser o futuro destes sectores depois da pandemia da Covid-19, a curto prazo torna-se importante encontrar formas de usar melhor o que se tem, retomar a trajectoria de sustentabilidade da dívida pública e normalizar as relações com os principais parceiros de apoio orçamental. Como se pode perceber da dinâmica dos indicadores da saúde, água e saneamento, os custos sociais de sub-utilizar o potencial existente e manter o status quo nas Finanças Públicas são demasiado altos para serem desconsiderados.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health - WASH / saúde - água; higiene e saneamento; health / saúde

Uma Logística Farmacêutica ainda distante de responder às preocupações de saúde do país: as fragilidades orçamentais - N'weti (N'weti, 2020)
A área de logística farmacêutica (LF) é vital pelo facto de assegurar que os medicamentos e produtos médicos estejam disponíveis no país e nos pontos de entrega e inclui seleção de medicamentos, quanti cação, procurement, controle de qualidade, armazenamento, transporte e distribuição. O Governo de Moçambique reconhece a importância deste sector e como parte da agenda de reforma do MISAU desenhou o Plano Estratégico de Logística Farmacêutica (PELF) juntamente com o respectivo Plano Operacional (2013). O PELF visa responder a necessidade de providenciar reformas a área de logística farmacêutica melhorando a gestão nanceira, procurement, inventariação, gestão do armazenamento, transporte, distribuição, uso de medicamentos e gestão de recursos humanos. Relatórios disponíveis apontam para a existência de vários desafios na implementação do PELF sendo que a falta de recursos financeiros é um dos maiores desafios para a implementação do quadro de recomendações deste documento. Em Moçambique a LF é actualmente uma das áreas menos favorecidas em termos de dotação orçamental cabendo-lhe 7% do total de envelope de recursos do sector da saúde projectados até 2019 (MISAU/DNPC, 2013). Esta tendência ao ser estacionária ao longo dos próximos 5 anos certamente estará em descompasso com a expansão e aumento da demanda pelos serviços públicos de saúde o que poderá comprometer a prestação do sector de saúde. A actual fonte de nanciamento e práticas de alocação orçamental na área de LF é também problemática. A estimativa da taxa de desperdício de medicamentos e consumíveis representa cerca de 13% do investimento total de $3,929 milhões de dólares da área de Logística Farmacêutica. Uma redução da taxa de desperdício para 5% implicaria numa economia de 332 milhões de dólares durante o PESS 2014 - 2019 (Dutta et al., 2014). Adicionalmente mais de 81% dos fundos para área de medicamentos são nanciados por parceiros externos (Dutta et al., 2014). Esta dependência de fundos externos é preocupante num cenário de incerteza do nanciamento externo ao sector de saúde (Dutta et al., 2014). Os níveis de satisfação da disponibilidade de medicamentos essenciais a nível central apesar de registarem progressos contrastam com a disponibilidade de medicamentos a nível das unidades sanitárias (MISAU, 2013, 2014). Várias Organizações da Sociedade Civil (OSC) incluindo a N ́weti, MSF o CIP tem denunciado sistemáticas rupturas de medicamentos nas unidades sanitárias das províncias do sul, centro e norte do país. Face as rupturas sistemáticas de medicamentos nas unidades sanitárias e a imprevisibilidade do nanciamento externo é crucial que o Governo de Moçambique incremente o volume de nanciamento para a área de LF sobretudo na base de recursos domésticos. A falta de recursos está a afectar grandemente a implementação do PELF e de igual modo a capacidade do sector de saúde em providenciar de forma e ciente serviços de saúde de qualidade.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; health / saúde

‘We all have the same right to have health services’: a case study of Namati’s legal empowerment program in Mozambique - Schaaf, Marta; Falcao, Joana; Feinglass, Ellie; Kitchell, Erin; Gomes, Nadja; Freedman, Lynn (BMC Public Health, 2020)
Background: Legal empowerment and social accountability are two strategies that are increasingly used to address gaps in healthcare in low- and middle-income countries, including failure to provide services that should be available and poor clinical and interpersonal quality of care. This paper is an explanatory case study of a legal empowerment effort that employs community paralegals and trains Village Health Committees (VHCs) in Mozambique. The research objective was to explore how community paralegals solved cases, the impact paralegals had on health services, and how their work affected the relationship between the community and the health sector at the local level. Methods: The case study had two components: (1) a retrospective review of 24 cases of patient/community grievances about the health system, and (2) qualitative investigation of the program and program context. The case reviews were accomplished by conducting structured in-depth interviews (IDIs) with those directly involved in the case. The qualitative investigation entailed semi-structured Key Informant Interviews (KIIs) with district, provincial, and national health managers and Namati staff. In addition, focus group discussions (FGDs) were held with Health Advocates and VHC members. Results: Case resolution conferred a sense of empowerment to clients, brought immediate, concrete improvements in health service quality at the health facilities concerned, and seemingly instigated a virtuous circle of rightsclaiming. The program also engendered incipient improvements in relations between clients and the health system. We identified three key mechanisms underlying case resolution, including: bolstered administrative capacity within the health sector, reduced transaction and political costs for health providers, and provider fear of administrative sanction. Conclusions: This study contributes to the limited literature regarding the mechanisms of legal empowerment case resolution in health systems and the impact of hybrid legal empowerment and social accountability approaches. Future research might assess the sustainability of case resolution; how governance at central, provincial, and district level is affected by similar programs; and to what extent the mix of different cases addressed by legal empowerment influences the success of the program.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; empowerment / empoderamento; health / saúde

Redressing the gender imbalance: a qualitative analysis of recruitment and retention in Mozambique’s community health workforce - Steege, Rosalind; Taegtmeyer, Miriam; Ndima, Sozinho; Give, Celso; Sidat, Mohsin; Ferrão, Clara; Theobald, Sally (Human Resources for Health, 2020)
Findings: In-depth interviews (n = 30), key informant interviews (n = 1) and focus group discussions (n = 3) captured experiences and perceptions of employment processes. Intra-household decision-making structures mean women may experience additional barriers to join the APE programme, often requiring their husband’s consent. Training programmes outside of the community were viewed positively as an opportunity to build a cohort. However, women reported difficulty leaving family responsibilities behind, and men reported challenges in providing for their families during training as other income-generating opportunities were not available to them. These dynamics were particularly acute in the case of single mothers, serving both a provider and primary carer role. Differences in attrition by gender were reported: women are likely to leave the programme when they marry, whereas men tend to leave when offered another job with a higher salary. Age and geographic location were also important intersecting factors: younger male and female APEs seek employment opportunities in neighbouring South Africa, whereas older APEs are more content to remain. Conclusion: Gender norms, roles and power dynamics intersect with other axes of inequity such as marital status, age and geographic location to impact recruitment and retention of APEs in Maputo Province, Mozambique. Responsive policies to support gender equity within APE recruitment processes are required to support and retain a gender-equitable APE cadre.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Mozambique Annual Report 2020: Responding to a Year of Crisis - Wojnar, Andrea M; Lomelin, Jessica; Baker, Daniel; Salu, Karlina; Macangira, Assane; Manjate, Epidauro (UNFPA, 2020)
In the case of Mozambique, the pandemic came on the heels of two destructive cyclones that had devastated large parts of the country in 2019 and whose consequences were still being felt. In northern Mozambique, increasing violence in Cabo Delgado province resulted in a surge of internally displaced persons into local communities in Cabo Delgado, Nampula and Niassa provinces. With host communities ill equipped to meet the needs of those displaced, this population movement created a new humanitarian crisis in the midst of the pandemic. Like all of our governmental, civil society and donor partners, the resilience of UNFPA was tested, and we had to adjust quickly after the first case of COVID-19 was confirmed in March and the Government declared a state of emergency. At the most basic level, women continued to get pregnant and babies were still being born, even in the middle of a pandemic. Addressing the needs of adolescent girls and young women could not be put on hold. Helping to meet the needs of the symbolic target of UNFPA’s work – “the 10-year-old girl” – could not wait until she was 11. Helping to meet her aspirations for the future, advocating and working for her growth and self-fulfillment as a woman leading a healthy, productive and violence-free life – these could not wait a year.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; youth / juventude

Social and Behaviour Change Communication Interventions in Mozambique - Cooper, Rachel (2019)
Social and behaviour change communication (SBCC) is the use of communication to change behaviours by positively influencing knowledge, attitudes and social norms at the individual and community level. Approaches to SBCC include, but are not limited to: media campaigns, peer educators and mentors, small group sessions, community dialogues and events, and digital tools. This rapid literature review focuses on SBCC interventions in Mozambique across four sectors: family planning (FP); girls’ empowerment; water, sanitation and hygiene (WASH), and nutrition. The most common SBCC approaches across the four sectors include: Inter-personal communication, Community participatory approaches, SMS based platforms, and Media channels. This review draws on evaluations of SBCC intervention, donor reports, and qualitative evidence collected by implementers and funders. There is a relatively large evidence base for FP and nutrition interventions, and a comparatively smaller one for WASH and girls’ empowerment. No lessons learned from integrating WASH and nutrition programming could be found during the course of this review. Although there are examples of nutrition programming including WASH in their counselling interventions, as well as calls for the development of multisectoral programmes. For example, in 2017, UNICEF signed a multi-sectoral proposal covering WASH, nutrition, and behaviour change funded by the EU. The programme will work in Nampula and Zambezia Provinces between 2017 and 2021.
Accepted: 2020-02-14T13:40:55Z Publisher: IDS
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; health / saúde; ⛔ No DOI found

Democratization of Health Services: Dynamics of Administrative Resistances (N'weti - comunicação para saúde, 2019)
This policy brief, apart from describing the dilemmas of the democratization process of health services it, aims to analyze its implications on the dynamics of social accountability in the health sector and, finally, to inform on possible ways for a more coherent democratization, considering the normative discourses
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; decentralization / descentralização; health / saúde

Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique - Khadiagala, Gilbert M.; Manhique, Jorge R. (WFD - Moçambique, 2019)
The inclusion of persons with disabilities is an essential element of a strong democracy and a just society. Persons with disabilities (PWDs) being included means that they have a full and equal opportunity to participate in society and in political decision-making processes, to develop their capacities, and to contribute to national progress Like everywhere, persons with disabilities in Mozambique face physical, social, economic and/or environmental barriers to participation. For example, 17 percent of persons with disabilities in Mozambique have been refused entry into a school or preschool because of their disability. Prior to its ratification of the International Convention on the Rights of People with Disability (ICCPD), which protects and promotes the rights and dignity of persons with disabilities, Mozambique had already pioneered progressive measures to promote the inclusion of persons with disability through specific principles in the Constitution of the Republic and the development of multisectoral plans on disability. Furthermore, the Mozambican Government proposed a new set of commitments that were presented at the London Summit in July 2018, reaffirming its adherence to the International Convention on the Rights of People with Disability. The Mozambican Minister for Gender, Children and Social Action, Her Excellency Cidália Manuel Chaúque Oliveira, today spoke at an event on 18th December to launch the study, ‘Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique.’ The study is the result of consultations with people with disabilities of different types and other stakeholders working to promote the rights of persons with disabilities (PWDs) in the Nampula, Beira and Maputo regions of Mozambique. The consulations aimed to find out about the socio-economic and political situations of PWDs and the barriers they face, as well as propose solutions to those problems. The consultation is part of the effort to establish a National Agenda for greater social, economic and political inclusion of PWDs in Mozambique. The study identifies the opportunities for, progress made, obstacles to, and consensus on national policies and strategies. It articulates a ways forward for building an inclusive society and achieving social justice. The study contibutes to Mozambique’s efforts work effectively towards national and international commitments to inclusive development. The study was undertaken as part of the Commonwealth Partnership for Democracy (CP4D) programme. It was carried out by WFD Mozambique in partnership with the Mozambican Association of People with Disability (ADEMO), the Mozambican Forum of Associations for People with Disability (FAMOD), and the Assembly of the Republic of Mozambique, in collaboration with the Ministry of Gender, Children and Social Action and with the technical advice of the Centre for Human Rights of the University of Pretoria in South Africa.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 - INS; ICF (INS/Mozambique, INE, PNCM, ICF, 2019)
O presente relatório resume os resultados do Inquérito Nacional sobre Indicadores de Malária em Moçambique, conduzido pelo Instituto Nacional de Saúde (INS), em colaboração com o Programa Nacional de Controlo da Malária (PNCM) e o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através The Demographic and Health Surveys (DHS) Program. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos Contra a Malária (PMI) e o Fundo das Nações Unidas para a Infância (UNICEF).
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Midwives’ perspectives on (dis)respectful intrapartum care during facility-based delivery in sub-Saharan Africa: a qualitative systematic review and meta-synthesis - Bradley, Susan; McCourt, Christine; Rayment, Juliet; Parmar, Divya (Reproductive Health, 2019)
Background: In the past decade, the negative impact of disrespectful maternity care on women’s utilisation and experiences of facility-based delivery has been well documented. Less is known about midwives’ perspectives on these labour ward dynamics. Yet efforts to provide care that satisfies women’s psycho-socio-cultural needs rest on midwives’ capacity and willingness to provide it. We performed a systematic review of the emerging literature documenting midwives’ perspectives to explore the broader drivers of (dis)respectful care during facility-based delivery in the sub-Saharan African context. Methods: Seven databases (CINAHL, PsychINFO, PsychArticles, Embase, Global Health, Maternity and Infant Care and PubMed) were systematically searched from 1990 to May 2018. Primary qualitative studies with a substantial focus on the interpersonal aspects of care were eligible if they captured midwives’ voices and perspectives. Study quality was independently assessed by two reviewers and PRISMA guidelines were followed. The results and findings from each study were synthesised using an existing conceptual framework of the drivers of disrespectful care. Results: Eleven papers from six countries were included and six main themes were identified. ‘Power and control’ and ‘Maintaining midwives’ status’ reflected midwives’ focus on the micro-level interactions of the mother-midwife dyad. Meso-level drivers of disrespectful care were: the constraints of the ‘Work environment and resources’; concerns about ‘Midwives’ position in the health systems hierarchy’; and the impact of ‘Midwives’ conceptualisations of respectful maternity care’. An emerging theme outlined the ‘Impact on midwives’ of (dis)respectful care. Conclusion: We used a theoretically informed conceptual framework to move beyond the micro-level and interrogate the social, cultural and historical factors that underpin (dis)respectful care. Controlling women was a key theme, echoing women’s experiences, but midwives paid less attention to the social inequalities that distress women. The synthesis highlighted midwives’ low status in the health system hierarchy, while organisational cultures of blame and a lack of consideration for them as professionals effectively constitute disrespect and abuse of these health workers. Broader, interdisciplinary perspectives on the wider drivers of midwives’ disrespectful attitudes and behaviours are crucial if efforts to improve the maternity care environment - for women and midwives - are to succeed.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Religion and Use of Institutional Child Delivery Services: Individual and Contextual Pathways in Mozambique - Cau, Boaventura Manuel; Agadjanian, Victor (International perspectives on sexual and reproductive health, 2019)
CONTEXT: Research on institutional child delivery in Sub-Saharan Africa typically focuses on availability and accessibility of health facilities. Cultural factors, including religion, that may facilitate or hinder the use of such services have not been well examined and remain poorly understood. METHODS: The relationship between religious affiliation and delivery in a health facility was explored using data from a household survey of 1,297 women aged 18-50 and a census of 825 religious congregations, both conducted in a predominantly Christian district in Mozambique in 2008. Multilevel logistic regression analyses were conducted to predict the likelihood of recent institutional delivery according to both individual religious affiliation and the concentration of religious congregations of certain denominations in the community of residence. RESULTS: Approximately 63% of deliveries occurred in a health facility. The odds of such deliveries were lower among women who belonged to Apostolic churches or had no religious affiliation than among members of Catholic or mainline Protestant churches, net of other factors (odds ratios, 0.5 and 0.6, respectively). In addition, regardless of a woman's religion, the odds that she had an institutional delivery increased by 9% for each additional Catholic or mainline Protestant congregation in her community of residence (1.1). CONCLUSIONS: Organized religion is associated with critical health outcomes in Mozambique and, potentially, in other Sub-Saharan African contexts. Policymakers should consider designing programs and interventions that promote the use of institutional delivery services among members of religious groups characterized by low use of these services and in areas where such religious groups have a strong presence.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Health equity monitoring is essential in public health: lessons from Mozambique - Llop-Gironés, Alba; Cash-Gibson, Lucinda; Chicumbe, Sergio; Alvarez, Francesc; Zahinos, Ivan; Mazive, Elisio; Benach, Joan (Globalization and Health, 2019)
Background: Countries must be able to describe and monitor their populations health and well-being needs in an attempt to understand and address them. The Sustainable Development Goals (SDGs) have re-emphasized the need to invest in comprehensive health information systems to monitor progress towards health equity; however, knowledge on the capacity of health information systems to be able do this, particularly in low-income countries, remains very limited. As a case study, we aimed to evaluate the current capacity of the national health information systems in Mozambique, and the available indicators to monitor health inequalities, in line with SDG 3 (Good Health and Well Being for All at All Ages). Methods: A data source mapping of the health information system in Mozambique was conducted. We followed the World Health Organization’s methodology of assessing data sources to evaluate the information available for every equity stratifier using a three-point scale: 1 - information is available, 2 - need for more information, and 3 an information gap. Also, for each indicator we estimated the national average inequality score. Results: Eight data sources contain health information to measure and monitor progress towards health equity in line with the 27 SDG3 indicators. Seven indicators bear information with nationally funded data sources, ten with data sources externally funded, and ten indicators either lack information or it does not applicable for the matter of the study. None of the 27 indicators associated with SDG3 can be fully disaggregated by equity stratifiers; they either lack some information (15 indicators) or do not have information at all (nine indicators). The indicators that contain more information are related to maternal and child health. Conclusions: There are important information gaps in Mozambique’s current national health information system which prevents it from being able to comprehensively measure and monitor health equity. Comprehensive national health information systems are an essential public health need. Significant policy and political challenges must also be addressed to ensure effective interventions and action towards health equity in the country.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - health information systems / saúde - sistema de informação de saúde; health - maternal and child / saúde - materno-infantil; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde

The Health Budget: The Disparity Between Political Discourse and Practice - N'weti (N'weti, 2019)
Key Messages: - Health is a human right and is constitutionally protected in Mozambique; - The health sector is considered a priority sector by the Government of Mozambique; - The health sector is amongst the least funded by the State Budget in the past four years, (with less than 8% on average), against the 15% assumed in Abuja; - For the year 2014, of the 762.8 million USD allocated to the health sector, 44% came from external sources (REO MOH, 2014). The combined PROSAUDE resources, and the speci c "off-budget" projects’ funding demonstrates the enormous reliance on external partners to support the country’s health strategy; - There is an urgent need to increase internal State Budget funding for the health sector to ensure sustainability.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; budget / orçamento; health / saúde

Obstacles to advancing women’s health in Mozambique: a qualitative investigation into the perspectives of policy makers - Qiu, Mary; Sawadogo-Lewis, Talata; Ngale, Katia; Cane, Réka Maulide; Magaço, Amilcar; Roberton, Timothy (Global Health Research and Policy, 2019)
Background: Despite substantial investment in women’s health over the past two decades, and enthusiastic government support for MDG 5 and SDG 3, health indicators for women in Mozambique remain among the lowest in the world. Maternal mortality stayed constant from 2003 to 2011, with an MMR of 408; the estimated HIV prevalence for women of 15–24 years is over twice that for men; and only 12.1% of women are estimated to be using modern contraception. This study explores the perspectives of policy makers in the Mozambican health system and affiliates on the challenges that are preventing Mozambique from achieving greater gains in women’s health. Methods: We conducted in-depth interviews with 39 senior- and mid-level policy makers in the Ministry of Health and affiliated institutions (32 women, 7 men). Participants were sampled using a combination of systematic random sampling and snowball sampling. Participants were asked about their experiences formulating and implementing health policies and programs, what is needed to improve women’s health in Mozambique, and the barriers and opportunities to achieving such improvement. Results: Participants unanimously argued that women’s health is already sufficiently prioritized in national health policies and strategies in Mozambique; the problem, rather, is the implementation and execution of existing women’s health policies and programs. Participants raised challenges related to the policy making process itself, including an ever-changing, fragmented decision-making process, lack of long-term perspective, weak evaluation, and misalignment of programs across sectors. The disproportionate influence of donors was also mentioned, with lack of ownership, rapid transitions, and vertical programming limiting the scope for meaningful change. Finally, participants reported a disconnect between policy makers at the national level and realities on the ground, with poor dissemination of strategies, limited district resources, and poor consideration of local cultural contexts. Conclusions: To achieve meaningful gains in women’s health in Mozambique, more focus must be placed on resolving the bottleneck that is the implementation of existing policies. Barriers to implementation exist across multiple health systems components, therefore, solutions to address them must also reach across these multiple components. A holistic approach to strengthening the health system across multiple sectors and at multiple levels is needed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Impacto das Uniões Prematuras na Educação, Saúde e Nutrição em Moçambique: Resumo do Documento - ROSC (ROSC - F;orum da Sociedade Civil para os Direitos da Criança, 2019)
As uniões prematuras constituem um dos principais problemas sociais na África Austral que, pelas suas consequências negativas em cadeia: gravidez precoce,desnutrição crónica,fístula obstétrica,abandono escolar,se tornam um problema igualmente económico, uma barreira ao desenvolvimento socioeconómico. No caso de Moçambique, o problema afecta cerca de metade das raparigas com menos de 18 anos, o que faz do país um dos cinco mais afectados a nível da Comunidade dos Países da África Austral (SADC). Para fazer face a este problema, várias acções têm sido levadas a cabo, entre campanhas de sensibilização, programas de resgate de meninas em situação de vida marital precoce, lobby e advocacia para o fortalecimento do quadro institucional e legal, bem como estudos para melhor informar as acções referidas. No entanto, quase todas as pesquisas feitas à volta das uniões prematuras têm sido na perspectiva sociológica ou antropológica. Por isso, o Fórum da Sociedade Civil para os Direitos da Criança (ROSC), no âmbito das acções da Coligação para a Eliminação dos Casamentos Prematuros (CECAP), com o apoio da OXFAM, através do Programa AGIR, decidiu realizar este estudo de perspectiva económica, para aferir o impacto que as uniões prematuras têm na educação, saúde e nutrição no país. Este estudo foi elaborado com quatro finalidades: primeira, contribuir para o debate sobre o impacto das uniões prematuras; segunda, elucidar aos actores-chave sobre as consequências das uniões prematuras para o desenvolvimento do país; terceira, despertar a consciência dos tomadores de decisão e da sociedade no geral sobre os impactos negativos das uniões prematuras na educação, saúde e nutrição; quarta e última finalidade, contribuir para despertar a atenção para a necessidade do desenho de programas, políticas e leis que visam mitigar os impactos negativos das uniões prematuras
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género; health / saúde

Introduction: The Accountability Politics of Reducing Health Inequalities: Learning from Brazil and Mozambique - Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P.; Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P. (Novos estudos CEBRAP, 2019)
Inequality is a key political issue of our times. It has political consequences, fuelling conflict and raising legitimacy chal‑ lenges for regimes around the world, in democratic and non‑demo‑ cratic settings alike. At the centre of these challenges is the question of accountability: who can be held accountable, on what basis, how and by whom for tackling or failing to tackle which inequalities. In the field of global health, inequality has long been a key issue. A significant body of work — in global health and health systems research — has approached the issue of health inequalities and in‑ equities by highlighting the role of social determinants (Marmot, 2015; Wilkinson; Pickett, 2006; Barreto, 2017). A more recent and less developed stream of work frames them in terms of political de‑ terminants: in other words, seeing them as issues that may be ad‑ dressed through politics as well as policy.
Publisher: Centro Brasileiro de Análise e Planejamento
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde

Rethinking health accountability in Mozambique: Beyond donors and government? (Institute of Development Studies, 2018)
As I explored in my previous blog, the health sector and provision of health services in Mozambique is an uneven playing field. Since 1980 it has been shaped by a range of donors who have strategically positioned themselves according to their political weight and ability to contribute with ‘commodities’ and financial resources. Although donors’ contributions […]
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; health / saúde

When a health system turns into a Tower of Babel: Mozambique's experience - Namburete, Denise (Institute of Development Studies, 2018)
Likened to the Tower of Babel legend, the Mozambican national health system speaks several languages and pursues a range of different interests, answering to a number of partners and other bilateral and multilateral actors who all have some kind of circumstantial and contextual interest. When the Paris Declaration on Aid Effectiveness was endorsed, Mozambique may […]
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde

Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
978-1-78118-441-7
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Inverted State and Citizens’ Roles in the Mozambican Health Sector - Dias, Jose; Tomé, Tassiana (IDS Bulletin, 2018)
This article aims to understand the inversion of roles between the state and citizens, by exploring its historical roots and current implications for processes of social accountability in Mozambique, particularly in the health sector. This is a practice-based reflection grounded in the evidence collected through the implementation of Community Scorecards in the health sector in 13 districts of Mozambique. The evidence has revealed a transfer of responsibilities from local governance institutions and service providers to the communities; diluting the frontiers between the state and citizens’ duties and rights, resulting in the inversion of roles. This inversion results in the minimisation of the state’s performance of its duties and accountability in the health sector to respond to local communities’ needs, allegedly due to the lack of financial resources. It also leads to the overburdening of local communities, who assume the responsibility of meeting their own demands, risking participation fatigue.
Accepted: 2018-05-01T10:02:21Z Publisher: Institute of Development Studies
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; Important; L - english / inglês; Northern PEA; accountability / responsabilização; health / saúde

New Action Plan for Health Promotion in Cabo Delgado (Mozambique) (2018)
In Cabo Delgado - Mozambique, we are giving support to the Provincial Health Directorate (DPS-CD) in developing an essential tool for the promotion of health in the Province: The Action Plan for Health Promotion.
Keywords: *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; health / saúde

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 Folheto (Brochure) - INS (2018)
O objectivo do IIM 2018 é disponibilizar as estimativas de indicadores demográficos e de saúde básicos, relacionados com a malária. As informações recolhidas através do IIM 2018 destinam-se a ajudar os decisores políticos e gestores do programa de controle de malária na avaliação e concepção de estratégias para melhorar a saúde da população do país.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA) 2015 - Ministério da Saúde- MISAU; Instituto Nacional de Estatística - INE; ICF (MISAU/Moçambique, INE, and ICF, 2018)
O presente relatório resume os resultados do Inquérito de Indicadores de Imunização, Malária e HIV/SIDA em Moçambique (IMASIDA 2015), conduzido pelo Instituto Nacional de Saúde (INS) do Ministério da Saúde (MISAU), em colaboração com o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através do Programa de Inquéritos Demográficos e de Saúde (Programa DHS). A assistência técnica adicional foi proporcionada pelo CDC (Centers for Disease Control and Prevention) dos Estados Unidos da América, através do seu escritório em Moçambique. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos para o Controlo da Malária (PMI), Fundo Global (FG-Rondas 8 e 9), Organização Mundial de Saúde (OMS), Fundo das Nações Unidas para a Infância (UNICEF), Aliança Internacional para a Saúde/Universidade de Washington (HAI/UW), Fundo das Nações Unidas para a População (FNUAP), Conselho Nacional de Combate ao HIV e SIDA (CNCS), através do seu Fundo Comum e Plano de Emergência do Presidente dos Estados Unidos para o Alívio da SIDA (PEPFAR), através do CDC.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Fast Facts from the 2018 Mozambique MIS - The DHS Program (2018)
The 2018 Mozambique Malaria Indicator Survey (IIM) provides population-based estimates on malaria indicators to inform strategic planning and program evaluation. The 2018 LMIS is the 6th survey to be conducted in Mozambique through The DHS Program.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Cidadania e Mudanças na Saúde e Educação em Moçambique: O Cartão de Pontuação Comunitária - Franco, Erika Lopez; Citizen Engagement Programme (CEP) (2017)
Este documento sumariza as aprendizagens feitas ao longo da implementação do Cartão de Pontuação Comunitária (CPC) no quadro do Programa Cidadania e Participação (CEP), o qual terminou em Dezembro de 2017. O CEP foi um programa de responsabilização social que tinha como objectivo final aumentar a influência dos cidadãos na melhoria da qualidade dos serviços de saúde e educação em Moçambique.
Accepted: 2018-04-13T12:59:17Z Publisher: (CEP) Citizen Engagement Programme / Cidadania e Participação
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; Northern PEA; access to services / acesso a serviços; citizenship & participation / cidadania e participação; community scorecard (CSC) / cartão de pontuação comunitária (CPC); education / educação; health / saúde

Maternal and Newborn Mortality: Community Opinions on Why Pregnant Women and Newborns Are Dying In Natikiri, Mozambique - Belo, C; Pires, P; Josaphat, J; Siemens, R; Rooke, E; Spence-Gress, C (International Journal of Research, 2017)
Background and objective: maternal and neonatal mortality rates in Mozambique are high, due to insufficient numbers of qualified health workers, lack of equipment and materials, referral system deficiency, difficulties to access health services and gender issues. This study assesses the barriers to health care access, regular attendance at ante natal consultations, institutional delivery and postnatal and neonatal follow-up. This is part of the baseline study for an implementation research project to reduce maternal and neonatal mortality in Natikiri, Nampula, Mozambique. Conclusion: local community members and health professionals were asked to state what they thought would be the best way to intervene. These ideas were then discussed further at a conference with health professionals and government representatives. Six intervention strategies to address identified problems were decided on and will be the basis for the ongoing implementation research project. They were: 1. Expanding family planning especially with adolescents. 2. Community based transport system for pregnant women. 3. Strengthening maternal and child health services by training maternity personnel in obstetrical emergency care and neonatal resuscitation. 4. Providing four quality prenatal visits. 5. Providing quality cesarean deliveries. 6. Supporting the Mozambican Government's campaign against bribery.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

Maternity care system in Maputo, Mozambique: Plans and practice? - Long, Qian; Madede, Tavares; Parkkali, Saara; Chavane, Leonardo; Sundby, Johanne; Hemminki, Elina (Cogent Medicine, 2017)
Mixed methods were used with various data sources to describe organisation and delivery of maternity care in Maputo city, Mozambique in early 2010s and to compare the plans with the service provision in practice. In the public health sector, maternity care was organised to be area based and hierarchical with a planned referral system. The provision of basic and emergency maternity care was publicly funded, largely dependent of donor funds, and free of charge for users. Even though Maputo City was better resourced than the rest of the country, there was a large lack of health professionals. Women’s choices and self-referrals, even to higher levels of care, were common, which broke the plans of areas responsibility, gate keeping and care by medical needs. Private services for maternity care had emerged for those who were able to pay, leading to dual practices of health professionals and shortage of care providers in the public system at odd hours. Information of maternity care was aggregate and poorly stored. The gap between “planned” services delivery and “practice” in a real-life requires overall health system strengthening to improve efficiency and effectiveness of health services delivery.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Desafio da articulação entre os cidadãos e os Comités de Qualidade e Humanização dos Cuidados de Saúde como órgãos de representação da comunidade - Dias, José (Centro de Aprendizagem e Capacitação da Sociedade Civil, 2017)
O Ministério da Saúde reconhece os Comités de Qualidade e Humanização dos Cuidados de Saúde nas Unidades Sanitárias como a principal forma de diálogo e ligação entre os serviços de saúde e as comunidades. Os Termos de Referência revistos, afirmam que o Comité de Qualidade e Humanização das Unidades Sanitárias constitui uma equipa de assessoria e coordenação ao processo de implementação da actividades de qualidade e humanização no âmbito da Unidade Sanitária. Destina-se a empreender uma política institucional de resgate de valores humanitários e de garantia de qualidade nos serviços de saúde, em benefício dos utentes e trabalhadores através da gestão participativa. Contudo, o sector de saúde dispõe também da Carta dos Direitos e Deveres do Doente, como instrumento que, no nosso entendimento, define o padrão da prestação de serviços, de comportamento, e concede espaço ao cidadão, individual ou colectivamente, para a exigência directa de serviços de saúde de qualidade. A este último propósito, por exemplo, cabe ressaltar que no quadro do Direito 16 (Direito a apresentar sugestões, queixas e reclamações) é estabelecido que através dos canais disponibilizados pelas Autoridades Sanitárias, os doentes têm direito a apresentar, individual ou colectivamente, petições, sugestões, reclamações ou queixas sobre a organização e o funcionamento dos serviços de saúde; e de ter as suas queixas atendidas prontamente e de maneira equitativa (MISAU, 2011). O que se apreende do exposto é que enquanto os Comités de Qualidade e Humanização funcionam numa lógica essencialmente de Democracia Representativa, a Carta dos Direitos e Deveres do Doente se insere numa abordagem de Democracia Participativa, buscando promover uma cidadania activa do doente/cidadão na sua interacção directa com as unidades sanitárias. O nosso artigo problematiza e discute as dinâmicas de representação e de participação activa do cidadão no processo da prestação de serviços de saúde. A nossa base de discussão é fundamentada em evidências de 15 distritos de actuação do Centro de Aprendizagem e Capacitação da Sociedade Civil (CESC), onde funcionam os Comités de Qualidade e Humanização, por um lado, e se implementa a abordagem de Responsabilização Social, usando ferramentas tais como Cartão de Pontuação Comunitária, por outro.
Keywords: G - Mozambique / Moçambique; Health PEA; L - portuguese / português; access to services / acesso a serviços; citizenship & participation / cidadania e participação; health / saúde

Estratégia Científica 2016-2015 - Instituto Nacional da Saúde - Moçambique (Instituto Nacional da Saúde - Moçambique, 2017)
A presente Estratégia Científica do Instituto Nacional de Saúde (INS) para 2016-2025 está alinhada com o Programa Quinquenal do Governo (2015-2019) e com o Plano Estratégico do Sector Saúde (PESS 2014-2019). No contexto global, a elaboração da presente Estratégia teve em conta os Objectivos de Desenvolvimento Sustentável (ODS), o Regulamento Sanitário Internacional (RSI) e a Agenda Global de Segurança Sanitária (GHSA). As principais diferenças entre a presente e anterior estratégia do INS são: 1) um horizonte temporal incrementado, sendo de 10 anos ao contrário de 5 anos na estratégia anterior; 2) uma ampliação das áreas programáticas estratégicas; 3) a inclusão de um robusto eixo estratégico de fortalecimento na área de gestão institucional. A Estratégia Científica do INS 2016-2025 está organizada em Programas e em Eixos Estratégicos. Os oito Programas desta Estratégia Científica reflectem as áreas temáticas consideradas como prioritárias. Estes Programas são: 1) Saúde e Ambiente, incluindo Saúde do Trabalhador; 2) Saúde Mental, Trauma e Violência; 3) Saúde da Mulher e da Criança; 4) Adolescente, Idoso e Outras Populações Vulneráveis; 5) Determinantes de Doenças Crónicas; 6) Doenças Transmitidas por Vectores, Negligenciadas e Zoonóticas; 7) Doenças Endémicas de Grande Impacto Sanitário; 8) Sistema de Saúde. Os cinco Eixos Estratégicos representam as funções essenciais de saúde pública. Este Eixos Estratégicos são: 1) Observatório Nacional de Saúde e Vigilância Epidemiológica; 2) Rede de Laboratórios de Referência em Saúde; 3) Pesquisa, Desenvolvimento Tecnológico e Inovação; 4) Ensino, Informação e Comunicação em Saúde; 5) Gestão e Desenvolvimento Institucional. Cada Programa e Eixo Estratégico tem um ou mais Objetivos Estratégicos e seus respectivos indicadores de impacto, cada um dos quais descreve a situação ideal que se pretende atingir a médio e longo prazo. Cada Objectivo Estratégico deve ser atingido mediante a execução de uma ou mais Acções cujo enunciado reflete num conjunto de Projectos/Actividades afins. Os Projectos são actividades com objectivos e temporalidade definidas, enquanto se denominam Actividades aquelas outras que são de carácter continuado, geralmente de gestão. Finalmente, cada Projecto/Actividade tem Produtos, Indicadores e Metas temporais e/ou quantitativas definidas. Os Projectos/Actividades temáticos encontram-se descritos em cada um dos oito programas, enquanto os Projectos/Actividades estruturantes encontram-se descritos em cada um dos cinco eixos estratégicos. A presente Estratégia Científica compreende 17 Objectivos Estratégicos, 19 Acções e 102 Projectos / Actividades.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - health services / serviços de saúde

Perspectives on the coordination of multisectoral nutrition in Mozambique and an emerging framework - Michaud-Létourneau, Isabelle; Pelletier, David Louis (Food Policy, 2017)
Multisectoral approaches represent a prominent ideological consensus, inﬂuenced by historical roots and the current political, ﬁnancial and institutional landscape, to address the multi-faceted and complex causes of most nutrition, public health and food problems. However, the implementation of multisectoral approaches presents tremendous challenges; one of the most often cited problems, in the literature and by practitioners, is coordination. This study investigates the perspectives of key national leaders on a range of issues regarding the coordination of a Multisectoral Action Plan for the Reduction of Chronic Undernutrition (PAMRDC) in Mozambique. Within this policy group, the principal researcher played the role of a researcher-participant for 14 months, and used Q methodology with a total of 21 key national leaders who had been actively engaged in coordination groups at the central level. Participants sorted 54 subjective statements on a range of issues that were present in the current national discourse. The results revealed four distinct perspectives. The Implementation perspective (n = 12) prioritized concrete actions to advance the operationalization of the plan, based on a guidance-based approach from the central level to the lower administrative levels. The Advocacy perspective (n = 3) emphasized advocacy to increase politicians’ awareness of the problem and of potential solutions to enhance political commitment. The Structuralist perspective (n = 3) was concerned with the development of structures and mechanisms to facilitate coordination, funding and improving communication between the government and donors. The People-centered perspective (n = 3) focused on the importance of mobilizing individuals to compensate for the sub-optimal structures and processes for coordination. Areas of convergence across the perspectives included: low capacity and skills that limit the work; the agency in charge of coordination (SETSAN) should exercise an increased leadership to facilitate the multisectoral work; and SETSAN should advocate to mobilize politicians and donors for resources. Areas of divergence related to the type of guidance from national to sub-national levels (prescriptive or not) and the functions to be carried out by SETSAN. This study highlights lack of clarity on the meaning of coordination and on the functions of the multisectoral coordination body that appear to arise for two reasons: the lack of an explicit and shared framework for the policy process and the complex nature of coordination itself. These results are examined through the lenses of several related literatures, including governance, public policy and political economy of nutrition, leading to a three-dimensional conceptual framework for coordination that distinguishes the coordination space, forms, and instruments. Global guidance, such as provided through the SUN movement, could support countries in overcoming their coordination challenges by facilitating an analysis of their decision-making processes in order to choose the functions for the coordination body based on a shared understanding of countries’ needs, context and opportunities. This paper moves the ﬁeld beyond a broad consideration of horizontal and vertical coordination within multisectoral initiatives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Austerity and the “sector-wide approach” to health: The Mozambique experience - Pfeiffer, James; Gimbel, Sarah; Chilundo, Baltazar; Gloyd, Stephen; Chapman, Rachel; Sherr, Kenneth (Social Science & Medicine, 2017)
Fiscal austerity policies imposed by the IMF have reduced investments in social services, leaving postindependence nations like Mozambique struggling to recover from civil war and high disease burden. By 2000, a sector-wide approach (SWAp) was promoted to maximize aid effectiveness. ‘Like-minded’ bilateral donors, from Europe and Canada, promoted a uniﬁed approach to health sector support focusing on joint planning, common basket funding, and streamlined monitoring and evaluation to improve sector coordination, amplify country ownership, and build sustainable health systems. Notable donors e including US government and the Global Fund e did not participate in the SWAp, and increased vertical funding weakened the SWAp in favor of non-governmental organizations (NGOs). In spite of some success in harmonizing aid to the health sector, the SWAp experience in Mozambique demonstrates how continued austerity regimes that severely constrain public spending will continue to undermine health system strengthening in Africa, even in the midst of high levels of foreign aid with the ostensible purpose of strengthening those systems. The SWAp story provides a poignant illustration of how continued austerity will impede progress toward Sustainable Development Goal 3 (SDG 3); “Achieve universal health coverage, including ﬁnancial risk protection, access to quality essential health-care services and access to safe, effective, quality and affordable essential medicines and vaccines for all”. However, the SWAp continues to offer an alternative model to health system support that can provide a foundation for resistance to renewed austerity measures.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; fiscal policy / política fiscal; health / saúde

População da Ilha de Moçambique queixa-se de cobranças ilícitas na maternidade - Televisão de Moçambique TVM (Televisão de Moçambique TVM, 2016)
Primeira sessão do dia aberto ao cidadão, uma iniciativa do conselho municipal da ilha de Moçambique para escutar as questões que atinjem os cerca de 50mil habitantes da primeira capital de Moçambique. As reuniões são realizadas nas comunidades para que de forma franca e aberta os munícipes possam apresentar os seus problemas
Keywords: G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Place, Time and Experience: Barriers to Universalization Of Institutional Child Delivery in Rural Mozambique - Agadjanian, Victor; Yao, Jing; Hayford, Sarah R (International perspectives on sexual and reproductive health, 2016)
CONTEXT: Although institutional coverage of childbirth is increasing in the developing world, a substantial minority of births in rural Mozambique still occur outside of health facilities. Identifying the remaining barriers to safe professional delivery services can aid in achieving universal coverage. METHODS: Survey data collected in 2009 from 1,373 women in Gaza, Mozambique, were used in combination with spatial, meteorological and health facility data to examine patterns in place of delivery. Geographic information system-based visualization and mapping and exploratory spatial data analysis were used to outline the spatial distribution of home deliveries. Multilevel logistic regression models were constructed to identify associations between individual, spatial and other characteristics and whether women's most recent delivery took place at home. RESULTS: Spatial analysis revealed high- and low-prevalence clusters of home births. In multivariate analyses, women with a higher number of clinics within 10 kilometers of their home had a reduced likelihood of home delivery, but those living closer to urban centers had an increased likelihood. Giving birth during the rainy, high agricultural season was positively associated with home delivery, while household wealth was negatively associated with home birth. No associations were evident for measures of exposure to and experience with health institutions. CONCLUSIONS: The results suggest the need for a comprehensive approach to expansion of professional delivery services. Such an approach should complement measures facilitating physical access to health institutions for residents of harder-to-reach areas with community-based interventions aimed at improving rural women's living conditions and opportunities, while also taking into account seasonal and other variables.
Keywords: G - Mozambique / Moçambique; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Effects of food price shocks on child malnutrition: The Mozambican experience 2008/2009 - Arndt, Channing; Hussain, M. Azhar; Salvucci, Vincenzo; Østerdal, Lars Peter (Elsevier, 2016)
A propitiously timed household survey carried out in Mozambique over the period 2008/ 2009 permits us to study the relationship between shifts in food prices and child nutrition status in a low income setting. We focus on weight-for-height and weight-for-age in different survey quarters characterized by very different food price inflation rates. Using propensity score matching techniques, we find that these nutrition measures, which are sensitive in the short run, improve significantly in the fourth quarter of the survey, when the inflation rate for basic food products is low, compared to the first semester or three quarters, when food price inflation was generally high. The prevalence of underweight, in particular, falls by about 40 percent. We conclude that the best available evidence points to food penury, driven by the food and fuel price crisis combined with a short agricultural production year, as substantially increasing malnutrition amongst under-five children in Mozambique.
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde; ⛔ No DOI found

Barriers and facilitators to health care seeking behaviours in pregnancy in rural communities of southern Mozambique - Munguambe, Khátia; Boene, Helena; Vidler, Marianne; Bique, Cassimo; Sawchuck, Diane; Firoz, Tabassum; Makanga, Prestige Tatenda; Qureshi, Rahat; Macete, Eusébio; Menéndez, Clara; von Dadelszen, Peter; Sevene, Esperança (Reproductive Health, 2016)
Background: In countries, such as Mozambique, where maternal mortality remains high, the greatest contribution of mortality comes from the poor and vulnerable communities, who frequently reside in remote and rural areas with limited access to health care services. This study aimed to understand women’s health care seeking practices during pregnancy, taking into account the underlying social, cultural and structural barriers to accessing timely appropriate care in Maputo and Gaza Provinces, southern Mozambique. Methods: This ethnographic study collected data through in-depth interviews and focus group discussions with women of reproductive age, including pregnant women, as well as household-level decision makers (partners, mothers and mothers-in-law), traditional healers, matrons, and primary health care providers. Data was analysed thematically using NVivo 10. Results: Antenatal care was sought at the heath facility for the purpose of opening the antenatal record. Women without antenatal cards feared mistreatment during labour. Antenatal care was also sought to resolve discomforts, such as headaches, flu-like symptoms, body pain and backache. However, partners and husbands considered lower abdominal pain as the only symptom requiring care and discouraged women from revealing their pregnancy early in gestation. Health care providers for pregnant women often included those at the health facility, matrons, elders, traditional birth attendants, and community health workers. Although seeking care from traditional healers was discouraged during the antenatal period, they did provide services during pregnancy and after delivery. Besides household-level decision-makers, matrons, community health workers, and neighbours were key actors in the referral of pregnant women. The decision-making process may be delayed and particularly complex if an emergency occurs in their absence. Limited access to transport and money makes the decision-making process to seek care at the health facility even more complex.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Gaza; GP - Maputo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

For an efficient, decentralised, transparent and inclusive health system - N'weti (N'weti, 2016)
Recommendations: 1. On planning and budgeting, greater coordination is recommended between planning (setting priorities) and budgeting (financial apportionment). Transformation of all District Health Services, Women and Social Action (SDSMAS) into Management Beneficiary Units (MBU) is necessary. 2. Stakeholders should bet more on application of national public financial management systems (PFM). The use of parallel financial systems instead of enabling the National Health System (NHS) to be more e cient hinders the enhancement of the sector’s PFM systems. 3. With regard to budgeting, zero-based budgeting implementation is recommended, replacing the incremental budgeting system. Zero-based budgeting is more realistic in so far as the health sector operation costs are concerned. 4. On the decentralisation and citizen participation component, the establishment of a national plan for decentralisation in the health sector is recommended. This plan would allow systematise local citizen participation mechanisms in the health system management and monitoring. 5. On revenue collection, the sector authorities need to explore areas of potential revenue already identified in Intellica’s 2013 research report, such as drug prescription, outpatient, medical certificate rates; and comply with the Decree 11/2007 of 30 May, which regulates tobacco consumption and sale, which has great potential to generate revenue for the health sector at the district level, by means of fines on the lawbreakers. 6. A Policy Brief drawn from the Public Expenditure Tracking Survey (PETS) in the Health Sector in Angoche, Bilene, Magude and Xai-Xai districts, and Chamanculo and José Macamo General Hospitals On expenditure performance, more and better coordination among stakeholders at district levels and Health Centres is recommended in order to avoid expenditure implementation costs in a fragmented and uncoordinated manner. 7. On procurement, accuracy improvement is recommended for the current legal framework implementation. This is to ensure that Procurement Management Units (PMUs) are practical; they can perform their tasks with independence, impartiality and professionalism. The direct award should always be treated as provided for in the law (an exception) and not deemed as the rule like what we have noticed occur in the researched cases. The document disorderliness of the Procurement Management Units portfolios can be solved with portfolio digitisation, ensuring more and better file and document handling, more control and additional transparency. 8. On transparency, recommendation to the Ministry of Health (MoH) is on the establishment of mechanisms which may ensure that sector o cials, who handle equal duties, should have the same understanding about procedures, not only in the health sector, but also in liaison with other sectors and society in general. When applying the Right to Information Act, Civil Society Organizations (CSOs) should now carry out awareness raising sessions and dialogue with sector o cials in order to reach mutual understanding on the added value that represents transparent public service management, with accountability and civil society influence, through monitoring and evaluation.
Keywords: *indexed; *non-public; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; GD - Bilene; GD - Magude; GD - Xai-Xai; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; budget / orçamento; decentralization / descentralização; health / saúde

Mapping the use of research to support strategies tackling maternal and child health inequities: evidence from six countries in Africa and Latin America - Vargas, Emily; Becerril-Montekio, Victor; Gonzalez-Block, Miguel Ángel; Akweongo, Patricia; Hazel, Cynthia N. A.; Cuembelo, Maria de Fatima; Limbani, Felix; Bernardo, Wanderley; Muñoz, Fernando (Health Research Policy and Systems, 2016)
Background: Striving to foster collaboration among countries suffering from maternal and child health (MCH) inequities, the MASCOT project mapped and analyzed the use of research in strategies tackling them in 11 low- and middle-income countries. This article aims to present the way in which research influenced MCH policies and programs in six of these countries – three in Africa and three in Latin America. Methods: Qualitative research using a thematic synthesis narrative process was used to identify and describe who is producing what kind of research, how research is funded, how inequities are approached by research and policies, the countries’ research capacities, and the type of evidence base that MCH policies and programs use. Four tools were designed for these purposes: an online survey for researchers, a semi-structured interview with decision makers, and two content analysis guides: one for policy and programs documents and one for scientific articles. Results: Three modalities of research utilization were observed in the strategies tackling MCH inequities in the six included countries – instrumental, conceptual and symbolic. Instrumental utilization directly relates the formulation and contents of the strategies with research results, and is the least used within the analyzed policies and programs. Even though research is considered as an important input to support decision making and most of the analyzed countries count five or six relevant MCH research initiatives, in most cases, the actual impact of research is not clearly identifiable. Conclusions: While MCH research is increasing in low- and middle-income countries, the impact of its outcomes on policy formulation is low. We did not identify a direct relationship between the nature of the financial support organizations and the kind of evidence utilization within the policy process. There is still a visible gap between researchers and policymakers regarding their different intentions to link evidence and decision making processes.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Challenges and opportunities for implementing evidence-based antenatal care in Mozambique: a qualitative study - Biza, Adriano; Jille-Traas, Ingeborg; Colomar, Mercedes; Belizan, Maria; Requejo Harris, Jennifer; Crahay, Beatrice; Merialdi, Mario; Nguyen, My Huong; Althabe, Fernando; Aleman, Alicia; Bergel, Eduardo; Carbonell, Alicia; et al. (BMC Pregnancy and Childbirth, 2015)
Background: Maternal mortality remains a daunting problem in Mozambique and many other low-resource countries. High quality antenatal care (ANC) services can improve maternal and newborn health outcomes and increase the likelihood that women will seek skilled delivery care. This study explores the factors influencing provider uptake of the recommended package of ANC interventions in Mozambique. Methods: This study used qualitative research methods including key informant interviews with stakeholders from the health sector and a total of five focus group discussions with women with experience with ANC or women from the community. Study participants were selected from three health centers located in Maputo city, Tete, and Cabo Delgado provinces in Mozambique. Staff responsible for the medicines/supply chain at national, provincial and district level were interviewed. A check list was implemented to confirm the availability of the supplies required for ANC. Deductive content analysis was conducted. Results: Three main groups of factors were identified that hinder the implementation of the ANC package in the study setting: a) system or organizational: include chronic supply chain deficiencies, failures in the continuing education system, lack of regular audits and supervision, absence of an efficient patient record system and poor environmental conditions at the health center; b) health care provider factors: such as limited awareness of current clinical guidelines and a resistant attitude to adopting new recommendations; and c) Users: challenges with accessing ANC, poor recognition amongst women about the purpose and importance of the specific interventions provided through ANC, and widespread perception of an unfriendly environment at the health center. Conclusions: The ANC package in Mozambique is not being fully implemented in the three study facilities, and a major barrier is poor functioning of the supply chain system. Recommendations for improving the implementation of antenatal interventions include ensuring clinical protocols based on the ANC model. Increasing the community understanding of the importance of ANC would improve demand for high quality ANC services. The supply chain functioning could be strengthened through the introduction of a kit system with all the necessary supplies for ANC and a simple monitoring system to track the stock levels is recommended.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Cabo Delgado; GP - Tete; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

N’weti’s Community Scorecard Experience in Nampula: a Case Study - Franco, Erika Lopez; Dumangane, Sansão (Institute of Development Studies and N'weti, 2015)
This case study was commissioned by N’weti Comunicação para a Saúde to explore the changes emerging from the implementation of an adapted version of the Community Scorecard (CSC) tool in 11 health facilities catchment areas in Nampula. This case study discusses how N’weti has adapted the Community Scorecard (CSC) tool to better improve the quality of the participation and prospects of accountability for citizens. The case study presents evidence that the adapted CSC tool has resulted in an increased awareness of rights, an improved relationship with the service providers, a revitalisation of the health unit Co-management Committees, citizens feeling that their voice is being heard, and N’weti is recognised by people and authorities as catalyser and legitimate mediator of this voice. However, challenges also surfaced which N’weti must reflect and learn from. The first relates to the meaningful control from regular citizens (rather than NGO staff members) of the institutionalisation, follow-up of commitments and advocacy actions derived from the implementation of a CSC process. Other challenges refer to social exclusion, the lack of a deeper understanding of power dynamics, and the fact that ignoring previous histories of citizen engagement and other contextual factors can be misleading as not all change can be directly attributed to the implementation of the CSC.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Meconta; GD - Moma; GD - Rapale; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Child Marriage and Adolescent Pregnancy in Mozambique: Policy Brief - Hodges, Anthony (UNFPA, Meninas e Não Noivas, UNICEF, 2015)
Child marriage is one of Mozambique’s most serious but largely ignored development challenges – requiring far greater attention from policy makers Child marriage rates are still very high despite a long-term decline, especially in marriage before the age of 15. Economic pressures and the incentive of bride price appear to be powerful factors driving parents to marry off their daughters at a young age. The high rates of child marriage cannot be allowed to continue without a vigorous response from the government, civil society and development partners.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Socio-economic and Community Health Baseline - Anadarko Mozambique (ExxonMobil, 2014)
This chapter outlines the socio-economic and health baseline of areas (both onshore and offshore) potentially affected by the Project. The chapter is structured into a number of sections, as follows: • Sections 9.2 and 9.3 provide a summary of the baseline and sources of information used to compile the baseline, respectively. • Section 9.4 defines the Project Area of Influence, providing both an overview of the geographic characteristics as well as the respective administrative divisions and governance structures. • Sections 9.5 to 9.7 provide an overview of Cabo Delgado Province (an important part of the Area of Indirect Influence) and aims to set the broader social, health and economic context in which the Project will be located. • Sections 9.8 to 9.14 provide a description of the social, health and economic characteristics of the Area of Direct Influence, which includes Palma District and the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.15 provides a description of the cultural and religious profile of the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.16 provides an overview of perceptions and expectations about the Project. • Section 9.17 provides an understanding of the shipping movements and types of vessels used within the Study Area. • Section 9.18 details the archaeology and cultural heritage baseline of the Afungi Project Site, based on both primary and secondary data.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; health / saúde; poverty / pobreza

Joint Assessment of the Mozambican Health Sector Strategic Plan (PESS, 2014-2019) - JANS - Joint Assessment of National Strategies (International Health Partnership, 2013)
Since independence in 1975, development in Mozambique has been guided by a sequence of Five Year Plans, (Planos Quinquenais de Desenvolvimento). In 2002 the Government of Mozambique (GOM) initiated a series of reforms in all development sectors, aiming to start a process of decentralisation and bringing management closer to the lower levels of state organisation (Provinces and Districts). For the Municipalities, a devolution model was chosen that is currently in the process of being rolled out to all municipalities in the country. It is within this context that the health sector initiated its Five Year Strategic Plans (Plano Estrategico do Sector da Saúde - PESS) in 2000 with the aim to gradually improve the health status of the people. The current PESS is the third of its kind (PESS III), representing a continuation of this good management practice in the country, aiming to improve access and quality of current services (Pilar 1), while at the same time continuing a series of Reforms within the health sector that aim to improve effectiveness and efficiency in overall service provision at all levels (Pilar 2). The health sector distinguishes four levels of service provision, going from Health Posts and Health Centres at the level of villages and sub-districts to District Hospitals to Provincial Hospitals and finally to the Central / Specialised Hospitals at the top of the health pyramid.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; decentralization / descentralização; health / saúde

Measuring Coverage in MNCH: Testing the Validity of Women's Self-Report of Key Maternal and Newborn Health Interventions during the Peripartum Period in Mozambique - Stanton, Cynthia K.; Rawlins, Barbara; Drake, Mary; dos Anjos, Matias; Cantor, David; Chongo, Lidia; Chavane, Leonardo; da Luz Vaz, Maria; Ricca, Jim (PLoS ONE, 2013)
Background: As low-income countries strive to meet targets for Millennium Development Goals 4 and 5, there is growing need to track coverage and quality of high-impact peripartum interventions. At present, nationally representative household surveys conducted in low-income settings primarily measure contact with the health system, shedding little light on content or quality of care. The objective of this study is to validate the ability of women in Mozambique to report on facility-based care they and their newborns received during labor and one hour postpartum. Methods and Findings: The study involved household interviews with women in Mozambique whose births were observed eight to ten months previously as part of a survey of the quality of maternal and newborn care at government health facilities. Of 487 women whose births were observed and who agreed to a follow-up interview, 304 were interviewed (62.4%). The validity of 34 indicators was tested using two measures: area under receiver operator characteristic curve (AUC) and inflation factor (IF); 27 indicators had sufficient numbers for robust analysis, of which four met acceptability criteria for both (AUC .0.6 and 0.75,IF,1.25). Two of these indicators are considered high demand and are recommended for incorporation into international survey programs: presence of a support person during labor/delivery and placement of the newborn skin to skin against the mother. Nine indicators met acceptability criteria for one of the validity measures. All 13 indicators are recommended for use in in-depth maternal/newborn health surveys. Conclusions: Women are able to report on some aspects of peripartum care. Larger studies may be able to validate some indicators that this study could not assess due to the sample size. Future qualitative research may assist in improving question formulation for some indicators. Studies of similar design in other low-income settings are needed to confirm these results.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Moçambique Inquérito Demográfico e de Saúde 2011 - Ministerio da Saude - MISAU/Moçambique; Instituto Nacional de Estatística - INE/Moçambique; ICF International (MISA/Moçambique, INE/Moçambique and ICF International, 2013)
O Inquérito Demográfico e de Saúde (IDS) em Moçambique faze parte dum programa internacional de inquéritos (MEASURE DHS) desenvolvido pelo ICF International através de um contrato com a USAID, com o propósito de apoiar aos governos e instituições privadas dos países em desenvolvimento na realização de inquéritos nacionais por amostragem, nas áreas de população e saúde. O Programa MEASURE DHS tem por objectivo: • Subsidiar a formulação de políticas e implementação de programas nas áreas de população e saúde; • Aumentar a base internacional de dados sobre população e saúde para acompanhamento e avaliação; • Aprimorar metodologia de inquérito por amostragem, e • Consolidar, na área de inquérito, a capacidade técnica da instituição executora no país participante do Programa. O Programa DHS teve início em 1984 e, desde então, já foram realizados inquéritos em mais de 70 países da América Latina, Caribe, África, Ásia e Leste Europeu.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

How active citizens can make a difference to improving service delivery in Mozambique: Phase 1: mapping citizen engagement programmes, initiatives and experiences - Programme, Citizen Engagement (2013)
The Citizen Engagement Program (CEP) supports citizens to monitor the quality of health and education service delivery in 4 of the 11 provinces of Mozambique, as well as to advocate for the improvement of the quality of those services at the district, provincial and national levels. The CEP aims at contributing towards the increased availability of relevant information for citizens to better access and benefit from services delivered by the public sector; improving citizens' capacity to assess service delivery and engage with service providers to improve the quality of health and education services at the primary and secondary levels; and supporting civil society organizations to leverage those findings within decision-making processes at higher levels. The programme will facilitate the dialogue between citizens / communities and service providers to improve the quality of services. The programme supports capacity-building, learning and experimentation, and will develop a robust system of monitoring and evaluation. The CEP will also analyse and build on experiences of service monitoring carried out by other actors and programmes, including other DFID and Irish Aid funded activities.
Accepted: 2017-12-05T13:07:47Z Publisher: (CEP) Citizen Engagement Programme / Cidadania e Participação
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; citizenship & participation / cidadania e participação; decentralization / descentralização; gender / género; health / saúde; ⛔ No DOI found

Juventude(s) e AIDS em Moçambique: Um Estudo Qualitativo no Distrito de Nhamatanda - Chicamisse, Francisco Armindo Zinhame (Universidade Federal de São Paulo, 2013)
O presente estudo pretende compreender como são desenvolvidas as ações de prevenção do HIV do Programa Geração Biz (PGB) direcionadas aos jovens dos 15-24 anos e, dessa forma buscar a compreensão da possível vulnerabilidade destes a infecção pelo HIV no distrito de Nhamatanda em Moçambique. Para o alcance deste desiderato baseei-me numa abordagem qualitativa, embasada no método etnográfico. No processo de coleta de dados privilegiei a observação participante, complementada por entrevistas semi-estruturadas e uma extensiva pesquisa bibliográfica. No distrito de Nhamatanda os jovens dos 15-24 anos constituem um dos segmentos populacionais mais afetados pelo HIV/AIDS, com uma taxa de prevalência estimada em 30,5% no ano de 2007, sendo por isso considerado um dos grupos mais vulneráveis a infecção pelo HIV. As ações de prevenção do HIV voltadas para este grupo são desenvolvidas pelo PGB, através das suas três componentes: escolar, comunitária e clínica. Entretanto, estas ações ainda estão assentadas na premissa de que a simples transmissão de informação implica na mudança de comportamentos dos jovens. Ademais, as ações de prevenção acabam tendo por vezes um caráter setorial e descontínuo, o que não permite o alcance de resultados mais duradouros no âmbito da prevenção do HIV. Os resultados deste estudo sugerem que as ações de prevenção do HIV ainda não se têm traduzido na redução considerável da referida vulnerabilidade dos jovens (15-24) a infecção pelo HIV neste distrito. Estas ações colocam por vezes os jovens em situações de maior suscetibilidade a infecção pelo HIV. Portanto, há uma necessidade de se repensar no modo como estas ações têm sido operacionalizadas, reelaborar os modelos pedagógicos que as norteiam e adequar os conteúdos semânticos das mensagens em função dos diferentes contextos socioculturais em que a epidemia se espraia.
Keywords: G - Mozambique / Moçambique; G - central / centro; GD - Nhamatanda; GP - Sofala; Health PEA; L - portuguese / português; access to services / acesso a serviços; health / saúde; youth / juventude

“Não basta introduzir reformas para se ter melhores serviços públicos”: subsídio para uma análise dos resultados das reformas no subsector de água rural em Moçambique - Forquilha, Salvador (Desafios para Moçambique 2013, 2013)
Em Setembro de 2012, o Governo de Moçambique anunciou a mudança de critérios para o cálculo das taxas de cobertura de abastecimento de água nas zonas rurais. Com efeito, de 500 pessoas para um poço ou furo equipado com uma bomba manual, num raio de 500 metros, passou -se para 300 pessoas para um poço ou furo equipado com uma bomba manual. Esta mudança de critérios acontece mais de 15 anos depois da aprovação da Política Nacional de Águas (PNA) e resulta da constatação de que, em muitos casos, os números oficiais estão longe de reflectir o que realmente se passa no terreno em termos de taxas de cobertura. Uma das consequências imediatas desta medida é, provavelmente, a revisão em baixa das taxas de cobertura de abastecimento de água rural, o que vai reforçar a ideia de que, à semelhança do que acontece com outros serviços públicos, o abastecimento de água rural ainda está longe de satisfazer as reais necessidades das populações.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; health - WASH / saúde - água; higiene e saneamento; rural development / desenvolvimento rural; ⛔ No DOI found

Saúde Para O Povo? Para Um Entendimento Da Economia Política E Das Dinâmicas Da Descentralização No Sector Da Saúde Em Moçambique - Weimer, Bernhard (Moçambique: Descentralizar o Centralismo? Economia Política, Recursos E Resultados, 2012)
Houve em 2011 três acontecimentos que revelaram as dimensões dos desafios que se colocam à gestão do Sistema Nacional de Saúde moçambicano em geral e ao Ministério de Saúde (MISAU) em particular. O primeiro foi uma auditoria externa das contas de 2009 do PROSAUDE II e do Fundo Global, realizada pela empresa de auditoria KPMG e entregue ao governo e aos seus parceiros internacionais em Junho de 2011. Esta auditoria revelou fraquezas consideráveis, nomeadamente em relação à auditoria interna e uma substancial diferença final não reconciliada entre os valores recebidos e os pagamentos efectuados. O segundo foi a crise de abastecimento de medicamentos, amplamente divulgada dos produtos farmacêuticos, quando os meios de comunicação noticiaram, num período de Março a Julho, que, no armazém farmacêutico central do MISAU, o CMAM,49 em Maputo, havia medicamentos no valor de pelo menos 2 milhões de USD que estavam fora de prazo; que os medicamentos se tinham esgotado nos hospitais públicos na Zambézia; e que grandes quantidades de medicamentos tinham desaparecido da farmácia do Hospital Central de Nampula.50 Os doadores recusaram um pedido de um montante adicional de 25 milhões de dólares para reabastecimento de medicamentos, feito pelo Ministro da Saúde em Março de 2011, argumentando que o governo teria que abordar e resolver as questões pendentes dos resultados da auditoria de 2009, antes de os doadores do PROSAUDE assumirem quaisquer compromissos de financiamento adicionais.51 Em terceiro lugar, pouco antes do fim do ano, o pessoal da saúde na Cidade de Nampula, incluindo os médicos, ameaçaram fazer greve, se não lhes fossem pagos os salários, três meses atrasados. Estes acontecimentos põem em relevo, em síntese, alguns dos principais desafios com que a gestão do sector da saúde se debate em Moçambique. Não se sabe até que ponto estes acontecimentos e o que eles revelam sobre a gestão de recursos no sector da saúde afectaram o funcionamento das unidades de saúde nas províncias e distritos, e o impacto sobre a saúde das pessoas doentes e da população em geral. Estas unidades dependem crucialmente de recursos (pessoal, financiamento e medicamentos) para o cumprimento da sua missão de controlar a doença e salvar vidas humanas, ou seja, para produzir os resultados de saúde que lhes compete alcançar, muitas vezes medidos com o indicador DALY.52 Neste artigo, não tentaremos avaliar o impacto das práticas de gestão no sector da saúde e os seus resultados em termos de vidas humanas. Tentaremos antes entender as dinâmicas políticas, económicas e institucionais que influenciam os resultados de saúde e o desempenho das unidades de saúde ao nível subnacional em Moçambique. O nosso argumento é que estas variáveis são determinadas não apenas por factores endógenos ao sector de saúde, como sejam as suas políticas e quadro regulamentar, a sua estrutura institucional, o grau de descentralização, e ainda os recursos que lhe são atribuídos e as suas capacidades de gestão. Também há factoresexógenos, como as decisões orçamentais do Ministério das Finanças, a Ajuda ao Desenvolvimento da Saúde (ADS)53 por parte dos doadores e as suas políticas e mecanismos de atribuição de fundos, como a abordagem sectorial integrada (SWAp)54 e o financiamento conjunto, bem como a mudança social e económica e as formas de governar um país, que produzem impactos decisivos no sistema de saúde e nos seus resultados. No que diz respeito à temática da descentralização da saúde, partimos, em primeiro lugar, do princípio que os ‘objectivos gerais da descentralização e a abordagem sectorial não são incompatíveis’, uma vez que tanto os primeiros como a segunda ‘têm por objectivo aumentar a eficiência técnica; incentivam uma maior participação; e põem a tónica na transparência e prestação de contas’ (Hutton, 2002: 3. Original em inglês). Em segundo lugar, chamamos a atenção para a necessidade de reconhecer um papel forte e normativo do Estado central nas políticas de saúde, na sua gestão, supervisão e questões de equilíbrio social, especialmente em matéria de cuidados de saúde primários, uma vez que a descentralização pode levar à diferenciação e à diversidade e não ao reforço da justiça social nos padrões e no acesso às unidades de saúde (Collins & Green, 1994). Como Booth sugeriu, o papel do Estado central é fundamental, nomeadamente em institucionalizar e supervisionar, do topo para a base, a disciplina de desempenho eficaz na componente de recursos humanos e na produção de serviços de qualidade a nível local (Booth, 2010: 34). Para este artigo, optámos por usar um quadro da análise político-económica para examinar alguns dos determinantes endógenos e exógenos. Do ponto de vista conceptual, a análise da economia política e da descentralização no sector da saúde pode ser estruturada de várias maneiras. Uma, é analisando as mudanças de epidemiologia, de características biomédicas dos corpos humanos e de ocorrênciaschave nos ciclos da vida humana (por exemplo, a fertilidade, a morbilidade ou mortalidade) como resultantes de intervenções por parte das instituições do sector da saúde, em condições sociais, económicas, ambientais e culturais em mudança. Esta abordagem é muitas vezes centrada na pobreza e assenta no pressuposto de que as mudanças institucionais, como a descentralização da prestação de serviços de saúde, conduzem a um aumento do bem-estar e a uma melhoria da saúde nas sociedades, se as intervenções institucionais (planos, programas, prestadores de serviços, etc.) forem ‘correctos’ e dispuserem de suficientes recursos financeiros e humanos, e capacidades, bem como de um quadro adequado de políticas. Dessa forma, julga-se que as taxas de fertilidade e mortalidade acabarão por diminuir, que as doenças infecciosas serão controladas e podem ser alcançados outros progressos no combate à pobreza e à doença (O’ Laughlin, 2010: 7).
Keywords: G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; health / saúde

Promoting Respectful Maternity Care in Mozambique - Reis, Veronica (USAID, 2012)
The objective of this document is to share the results of work undertaken in Mozambique to promote respectful health care, particularly in maternal and neonatal care. With its origins in “humanization of care” efforts in Latin America, this approach centers on the woman and her family and is grounded by principles of ethics and respect for human rights. The approach recognizes a client’s cultural background, and views the client as a person with values and expectations that should be respected during the provision of health care. Respectful maternity care (RMC) emphasizes the fundamental rights of the mother, newborn, and family, and recognizes that childbirth is a deeply personal experience for each woman and her family. In addition, RMC ensures that the client has timely access to health information, privacy, and evidence-based care. Promoting RMC can result in many benefits, including increased service utilization and better health outcomes. It is known that women refuse care from health providers who treat them poorly, even if these providers are capable of preventing or managing obstetric or newborn complications. In countries where a large proportion of births occur outside health facilities, RMC can contribute to increased uptake of maternal and newborn health (MNH) services.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Political economy of the health sector in Mozambique: Towards an understanding of its features, dynamics and challenges - MAP Consult (2012)
The powerpoint has the same objective as the article (see related section). ——- The present study was commissioned by the Department for International Development (DFID) in Mozambique. As a piece of independent research on the political economy of the health sector, it is considered to inform DFID’s health sector support programme for the period 2012-2016 and to lead to more in-depth inquiries of Mozambique’s health sector. The latter has witnessed a number of institutional, management, financial and governance challenges in the past few years, including a change in leadership considered important for the sector. The objective of this consultancy is to inform the development of a health sector support programme for the Government of Mozambique and to highlight particular political economy challenges and opportunities that DFID Mozambique should take into account in supporting PROSAUDE.
Keywords: *non-public; G - Mozambique / Moçambique; Health PEA; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; health / saúde

Political economy of the health sector in Mozambique: Towards an understanding of its features, dynamics and challenges - Weimer, Bernhard; Cumbi, Amelia J.; Macuane, José Jaime (MAP Consult, 2012)
The present study was commissioned by the Department for International Development (DFID) in Mozambique. As a piece of independent research on the political economy of the health sector, it is considered to inform DFID’s health sector support programme for the period 2012-2016 and to lead to more in-depth inquiries of Mozambique’s health sector. The latter has witnessed a number of institutional, management, financial and governance challenges in the past few years, including a change in leadership considered important for the sector. The objective of this consultancy is to inform the development of a health sector support programme for the Government of Mozambique and to highlight particular political economy challenges and opportunities that DFID Mozambique should take into account in supporting PROSAUDE.
Keywords: *non-public; *tagged; G - Mozambique / Moçambique; L - english / inglês; decentralization / descentralização; health / saúde

Effects of food price shocks on child malnutrition: the Mozambican experience 2008/09 - Arndt, Channing; Hussain, M. Azhar; Østerdal, Lars Peter (World Institute for Development Economics Research (WIDER), 2012)
A propitiously timed household survey carried out in Mozambique over the period 2008-09 permits us to evaluate the short-to-medium run relationship between sudden shocks to food prices and child nutrition status. We link local price inflation with child malnutrition status. We find that the prevalence of underweight amongst children rises in response to a higher inflation rate for basic food products. Stunting and wasting malnutrition measures are mostly insensitive to the inflation rate. The very high food inflation during 2008/09 was responsible for an extra 39,000 moderately underweight and 24,000 severely underweight children.
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde

Abastecimento De Água Nas Zonas Rurais: Avaliação Dos Progressos Para a Prestação De Serviços Sustentáveis - Munguambe, Carlos Gideon José; Jesus, Vitória Afonso Langa de (IRC International Water and Sanitation Centre, 2011)
This study presents an analytical ‘picture’ of the rural water sub-sector in Mozambique, describing the legal framework, mechanisms for coordination, harmonisation, funding, accountability, participation and supervision. The study was commissioned for the Sustainable Services at Scale, or Triple-S, initiative, which aims to contribute to improving the sustainability of global rural water supply. According to the general population census carried out in 2007, Mozambique had a total population of 20,226,296, 70.2% of whom live in rural areas, with a water coverage rate of only 54%.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; decentralization / descentralização; health - WASH / saúde - água; higiene e saneamento; health / saúde

Health Commodity Security Project - World Bank (World Bank, 2010)
Information document about the Health Commodity Security Project. It is divided in the sections below: - Country and Sector Background - Objectives - Rationale for Bank Involvement - Description - Financing - Implementation - Sustainability - Lessons Learned from Past Operations in the Country/Sector - Safeguard Policies (including public consultation) - List of Factual Technical Documents - Contact point - For more information contact
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; health / saúde

“All I Eat Is ARVs:” The Paradox of AIDS Treatment Interventions in Central Mozambique - Kalofonos, Ippolytos Andreas (Medical Anthropology Quarterly, 2010)
The number of people on antiretroviral treatment in Mozambique has increased by over 1,500 percent since it first became free and publicly available in 2004. The rising count of “lives saved” seems to portray a success story of high-tech treatment being provided in one of the poorest contexts in the world, as people with AIDS experience dramatic recoveries and live longer. The “scale-up” has had significant social effects, however, as it unfolds in a region with a complicated history and persistent problems related to poverty. Hunger is the principal complaint of people on antiretroviral treatment. The inability of current interventions to adequately address this issue leads to intense competition among people living with HIV/AIDS for the scarce resources available, undermining social solidarity and the potential for further community action around HIV/AIDS issues. Discourses of hunger serve as a critique of these shortcomings, and of the wider political economy underlying the HIV/AIDS epidemic.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - central / centro; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

APRM Country Review Report Mozambique - República de Moçambique (República de Moçambique, 2009)
The major cross-cutting issues which featured prominently in all the thematic areas are highlighted below. A comprehensive approach is needed to address these issues as they have wider ramification for the various dimensions of governance in Mozambique. The following are the major thirteen crosscutting issues emerging from this report: Poverty and Inequality; Party/government/business dichotomy; HIV/AIDs; Land Ownership; High levels of illiteracy; High aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. CONCLUSION: The remarkable recovery that Mozambique has made since the end of the civil war in 1992 should make the people proud of their accomplishments. Over the last two decades, Mozambicans has made considerable progress in rebuilding its political, economic and social institutions, with noticeable progress. There is no doubt that Mozambicans can build on the successes highlighted in this report, while addressing the challenges in a vigorous manner, in order for the country to rapidly move forward. With its abundant natural resources, Mozambicans can exploit these resources for the benefit of the majority of its people. But this will be difficult to achieve without pragmatic and innovative solutions to the challenges arising from both the thematic and cross-cutting issues identified by this report.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; governance / governação; health / saúde; natural resources / recursos naturais; poverty / pobreza

The group effect: Social cohesion and health outcomes - Bruhn, John (Springer New York, NY, 2009)
Sociologists and anthropologists have had a long interest in studying the ways in which cultures shaped different patterns of health, disease, and mortality. Social scientists have documented low rates of chronic disease and disability in non-Western societies and have suggested that social stability, cultural homogeneity and social cohesion may play a part in explaining these low rates. On the other hand, in studies of Western societies, social scientists have found that disease and mortality assume different patterns among various ethnic, cultural and social-economic groups. The role of stress, social change and a low degree of cohesion have been suggested, along with other factors as contributing to the variable rates among different social groups. Social cohesion has been implicated in the cause and recovery from both physical and psychological illnesses. Although there has been a large amount of work established the beneficial effects of cohesion on health and well-being, relatively little work has focused on HOW increased social cohesion sustains or improves health. This work is based on the premise that there are risk factors, including social cohesion that regulate health and disease in groups. One of the challenges is how to measure social cohesion - it can be readily observed and experienced but difficult to quantify. A better understanding of how social cohesion works will be valuable to improving group-level interventions. © Springer Science+Business Media, LLC 2009. All rights reserved.
Journal Abbreviation: tThe Group Effect: Social Cohesion and Health Outcomes Pages: 171 Publication Title: tThe Group Effect: Social Cohesion and Health Outcomes
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; health / saúde

Programas de saúde materno-infantil em Moçambique: marcos evolutivos e a inserção da enfermagem (Programs of maternal and infant health in Mozambique: gradual landmarks and the insertion of nursing) - Lourenço, Maria Acácia Ernesto; Tyrrell, Maria Antonieta Rubio (Escola Anna Nery, 2009)
See english abstract below. Pesquisa centrada nas políticas públicas do governo moçambicano para o setor da saúde, com foco voltado para programas de assistência à saúde materno-infantil. Tem o propósito de apresentar contextos básicos para a reflexão sobre a filosofia da implantação e implementação dos programas e a inserção da Enfermagem, mostrando seus marcos evolutivos. Constatou-se que, na década 70, o Sistema Nacional de Saúde adotou o Programa de Proteção Materno-Infantil, que na década de 80 ficou concebido como Programa de Saúde Materno-Infantil e, posteriormente, na década 90, ficou inserido no Programa Nacional Integrado de Saúde Materno-Infantil e Planejamento Familiar, Programa Alargado de Vacinação, Saúde Escolar e do Adolescente, incluindo Saúde Sexual e Reprodutiva. A inserção da Enfermagem foi evidenciada na implementação das ações assistenciais. Os marcos evolutivos foram: a introdução dos cursos específicos de Enfermagem em saúde materno-infantil do nível básico ao superior e abrangência dos serviços do Programa Nacional Integrado. ABSTRACT For the interest to know about the public Policies of Mozambican government to the Health sector, this research put much emphasis on the process of implantation and implementation of assistance programs to maternal health looking at reflection about the philosophy of including nursing through ever-changing world or marked changes. Established in the 1970s, the National Health System came up with a maternal health protection program which in the 1980s was drawn into Maternal Health Program. This, in the 1990s was included in the National integrated program of maternal health and family planning, integrating a broad vaccination program, school health and adolescent sexual reproductive health. The inclusion of nursing in the implementation of integrated program became as the evidence through action assistances. The evolutional signs were the introduction of specific courses of Maternal and Infant Health Nursing from basic to superior levels, including the service of National Integrated Program.
Publisher: UFRJ
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - portuguese / português; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Gender and Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Tuominen, Minna (Chr. Michelsen Institute, 2009)
The main objective of this report is to capture the local configurations of gender relations in Nampula, by focussing on one rural and one urban area in the province. The former is the coastal and rural district of Mossuril, which is considered one of the most deprived districts in the province, both in terms of material poverty and human development (MAE 2005). The urban areas are Muatala and Namutequeliua, which are two of the most populous bairros in the city of Nampula and largely inhabited by migrants from the coast and hence share historical and sociocultural roots with Mossuril.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mossuril; GP - Nampula; Health PEA; L - english / inglês; education / educação; employment / emprego; gender / género; health / saúde; poverty / pobreza

Capacity Strengthening in the Least Developed Countries (ldcs) for Adaptation to Climate Change (clacc): Climate Change and Health in Mozambique - Bambaíge, Albertina João; Cuamba, Boaventura; Hauengue, Maria dos Anjos (International Institute for Environment and Development (IIED), 2008)
The relationship between climate change and its effects on human health has been widely studied. Increases in temperature and variations in precipitation can exacerbate a number of human diseases including respiratory infections, malnutrition, vector and water borne diseases such as malaria and cholera. Besides all efforts undertaken by the Mozambican Government to reduce poverty and meet the MDGs targets, it is clear that climate change effects will influence negatively in meeting these targets. Damages caused by floods in Mozambique undermine economic growth rates of the country. Mainstreaming climate change adaptation into government policies would strengthen the capacity of the country to deal with climate change impacts. Climate change is a reality and the impacts on health are great with the poor at most risk. Efforts must be done nationally at all levels to come up with a proactive approach since all actors in the Mozambican society are directly or indirectly affected. This must include clear policies and strategies to deal with impacts of climate change on health; intersectoral approaches for strengthening the implementation of these policies and a greater support from those wealthy in resources and knowledge for minimizing the risks and increase community's adaptation capacity. The case study included in this country report highlights the relationship between climate change and human health through an analysis of malaria and cholera data taking the example of the 2000/2001 floods, which were considered the worst in the last fifty years. Adaptation practices and the adaptive capacity of the country during floods periods, policies and strategies are also discussed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; government policy / politica governamental; health / saúde; institutions / instituições; natural disasters / desastres naturais

Toward Gender Equality in Mozambique - Van den Bergh-Collier, Edda (Swedish International Development Cooperation Agency (SIDA), 2007)
This is an update of the previous Gender Profi le for Mozambique which was produced in 2000. Sida produces gender profi les for several countries with the purpose of providing a short and concise summary of the gender equality situation in partner countries. The profi e is a desk study reviewing and compiling available statistical material that may be of interest to anyone interested in women’s social, economic and legal position and understanding gender relations in Mozambique. The human development indicators show that signifi cant gender gaps exist in Mozambique. Thus a study of gender relations must repeatedly stress the relative deprivation of women in relation to men. The present profile emphasizes data that illustrates the relative position of men and women rather than attempting to capture and analyze gender relations in the whole country. A detailed discussion of gender relations for each thematic area would require extensive data and sociological/anthropological literature on the construction and dynamics of power relations between men and women in relation to that specifi c aspect of public and private life. For the most part, this kind of data is not available in Mozambique. Thus, the profile gives an overview of the types of issues women face as well as a brief indication of what is being done to address these challenges. Sida has developed generic terms of reference that identify specific issues and topics to be dealt with in individual country profi les. While the updated country profi le for Mozambique addresses all of the issues and topics described in the generic terms of reference, the data is presented in a specific sequence in order to more closely reflect the structure of the PARPA (Poverty Reduction Programme) and PES (Social and Economic Plan) of the Government of Mozambique. The PARPA and PES are central planning instruments for the Government; it is thus considered that this structure highlights potential linkages between Government priorities and Sida’s own development cooperation planning.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; governance / governação; health / saúde; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; land governance / gestão de terra; poverty / pobreza; youth / juventude

Consultoria sobre a Abolição das Taxas aos Utilizadores do Serviço Nacional de Saúde (SNS) em Moçambique - Cabral, Antonio Jorge Rodrigues (Instituto de Higiene e Medicina Tropical da Universidade Nova de Lisboa, 2007)
Existem actualmente taxas de utente cobradas em grande parte dos serviços de saúde públicos, em Moçambique. No entanto, historicamente, o partido no poder, a FRELIMO, tem sido bastante favorável a uma situação de serviços básicos de saúde gratuitos, e considera que a eliminação de barreiras de acesso à educação e saúde básicas constituem elementos fundamentais da estratégia de redução de Pobreza e de êxito nas Metas de Desenvolvimento do Milénio. O Governo de Moçambique considera ainda que a permanência das taxas mantém aberta a porta para a cobrança de taxas ilegais. A experiência de países vizinhos e a eliminação das taxas de matrícula no Ensino Básico em Moçambique constituíram motivações adicionais aos responsáveis do sector para que a viabilidade da remoção das taxas fosse avaliada. Esperava-se desta consultoria: i) uma avaliação da aplicação actual das taxas de utente; ii) uma síntese sobre o provável impacto esperado da abolição das taxas de utente nos serviços básicos de saúde em Moçambique, em especial na carga de trabalho dos funcionários da saúde e nos custos recorrentes no Sector da Saúde; iii) uma síntese dos pontos de vista da população em relação as condições de acesso aos cuidados de saúde, e dos pontos de vista de outros intervenientes em relação as taxas de utente no sector da saúde.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde

Governance, management and performance in health and education facilities in Bangladesh: findings from the Social Sector Perforamnce Qualitative Study - Oxford Policy Management (Oxford Policy Management, 2007)
This report presents findings from the Social Sector Performance Qualitative Study (SSPQS). The SSPQS was designed as a follow-up to the Social Sector Performance Surveys (SSPS), which were public expenditure tracking surveys undertaken in the primary and secondary education and government health and family planning systems between 2004 and 2006. In many respects, the SSPS findings were positive, documenting that systems of health and education service provision were functioning. While there were problems, including of corruption or leakage and poor quality services, the provision of health and education services was found to be reasonably effective within their given goals and resource constraints. The SSPQS was designed to use qualitative methods to triangulate, explore and illustrate selected findings from the SSPS. The research on schools drew on the Heneveld-Craig framework for analysing school effectiveness. Applied here, this entailed a focus on understanding how the quality of supporting inputs (parental and community participation, supervision and material inputs) and enabling conditions (the effectiveness of school management and the incentives of teachers), relate to the quality or performance of the facility. To explore the governance of schools and health facilities, the research also drew on the analytical framework developed in the World Development Report 2004 to unearth accountability mechanisms linking users, providers and policy makers. The main findings of the report are presented in Sections 3 to 5.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; education / educação; governance / governação; health / saúde

War and reconstruction in northern Mozambique - Brück, Tilman (The Economics of Peace and Security Journal, 2006)
The article discusses some of the economic effects of war in northern Mozambique. It indicates how the historical and structural features of the economy of northern Mozambique restricted post-war reconstruction and post-war poverty alleviation. These features include the dominance of only a few cash crops for export, the absence of much rural trading, poor communication infrastructure, and weak political and state institutions. The specific nature of the internal war further weakened the state through the collapse of tax revenue and export earnings and the massive growth of debt and aid, of which little reached rural northern Mozambique. The article also summarizes key aspects of the geography, climate, markets, and social institutions of northern Mozambique, which define the potential production opportunities for peasant households. Finally, the article suggests how post-war reconstruction could have been more effective in achieving faster post-war poverty alleviation in northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; conflict - civil war / conflito - guerra civil; health / saúde

Moçambique Inquérito Demográfico e de Saúde 2003 - Ministerio da Saude - MISAU/Moçambique; Instituto Nacional de Estatística - INE/Moçambique; ICF International (MISA/Moçambique, INE/Moçambique and ICF International, 2005)
O Inquérito Demográfico e de Saúde (IDS) em Moçambique faze parte dum programa internacional de inquéritos (MEASURE DHS) desenvolvido pelo ICF International através de um contrato com a USAID, com o propósito de apoiar aos governos e instituições privadas dos países em desenvolvimento na realização de inquéritos nacionais por amostragem, nas áreas de população e saúde. O Programa MEASURE DHS tem por objectivo: • Subsidiar a formulação de políticas e implementação de programas nas áreas de população e saúde; • Aumentar a base internacional de dados sobre população e saúde para acompanhamento e avaliação; • Aprimorar metodologia de inquérito por amostragem, e • Consolidar, na área de inquérito, a capacidade técnica da instituição executora no país participante do Programa. O Programa DHS teve início em 1984 e, desde então, já foram realizados inquéritos em mais de 70 países da América Latina, Caribe, África, Ásia e Leste Europeu.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Endangering safe motherhood in Mozambique: prenatal care as pregnancy risk - Chapman, Rachel R. (Social Science & Medicine, 2003)
Despite high infant and maternal mortality rates, many Mozambican women with access to prenatal services delay prenatal clinic consultations, limiting opportunity for prevention and treatment of preventable pregnancy complications. Ethnographic research, interviews with health providers and longitudinal pregnancy case studies with 83 women were conducted in Central Mozambique to examine pregnant women's underutilization of clinic-based prenatal services. The study found that pregnancy beliefs and prenatal practices reflect women's attempts to influence reproduction under conditions of vulnerability at multiple levels. Women reported high maternal reproductive morbidity, frequent pregnancy wastage, and immense pressure to bear children throughout their reproductive years. Reproductive vulnerability is intensified by poverty and an intense burden placed on poor, peri-urban women farmers for family subsistence and continuous fertility in a period of economic austerity, land shortages, and increasing social conflict and inequality. In this environment of economic insecurity exacerbated by congested living conditions, women report competing for scarce resources, including male support and income. This vulnerability heightens women's perceptions that they and their unborn infants will be targets of witchcraft or sorcery by jealous neighbors and kin. They respond by hiding pregnancy and delaying prenatal care. Within the context of women's perceived reproductive risks, delayed prenatal care can be seen as a strategy to protect pregnancy from purposeful human and spirit harm. Women mobilized limited resources to acquire prenatal care outside the formal clinic setting. It is concluded that provision of clinical prenatal services is insufficient to reduce reproductive risks for the most socially and economically marginal since it is their vulnerability that prevents women from using available services. Confidential maternity services and social safety nets for greater economic security are recommended.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil

New Rules, New Roles: Does PSP Benefit the Poor? Small-Scale Private Sector Participation in Niassa, Mozambique - Jose Atanasio David; Lindsey Breslin (Estamos organização comunitária, 2003)
This case study has attempted to show that the implementation of a policy mechanism like PSP in water and sanitation in a context like Niassa is highly unlikely to achieve the development impacts intended. It appears that the concept “PSP” itself is erroneous; it assumes that there is a private sector wishing to participate, and that public sector delivery is the key obstacle to private involvement. Equally erroneous is the idea that the private sector can just emerge from market mechanisms that are assumed to be existent. The market itself, and he relationships that typically exist within it, need to be constructed first. Niassa is an example of an extremely impoverished area where the cashpoor local economy and damaged social institutions currently could not support and sustain the emergence of a viable private sector.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; health - WASH / saúde - água; higiene e saneamento; health / saúde; private sector / setor privado

Discovering normality in health and the reproductive body : proceedings of a workshop held at the Program of African Studies Norhtwestern University - Bledsoe, Caroline; LaRay, Denzer; Glassman, Jonathon; Schoenbrun, David; Ebeling, Mary F. E.; Hansen, Karen Tranberg (Northwestern University's Program of African Studies, 2002)
The papers and discussions included in this collection are the product of a workshop, “Discovering Normality in Health and the Reproductive Body,” held in March, 2001 at Northwestern University's Program of African Studies. The idea for the workshop stemmed from a history of collaborations among Caroline Bledsoe, Jane Guyer, and Kuate Defo Barthélemy on topics of fertility, health, and research methodology. The workshop itself grew out of a commitment to continue that conversation and to expand it to a wider range of people and disciplines. The disciplines represented were wideranging indeed. They included sociocultural anthropology, biological anthropology, history, reproductive biology, history of medicine, public health, and obstetric medicine. The focus of the workshop was Africa, but we also included important comparative cases on South Asia and the Netherlands. In addition we have included those of the discussants' excellent and provocative comments that were available, some of the rapporteurs' notes, and a full list of the participants.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

Improving Health for the Poor in Mozambique: The Fight Continues - Chao, Shiyan; Kostermans, Kees (International Bank for Reconstruction and Development / The World Bank, 2002)
The health sector in Mozambique has made significant progress in terms of increasing coverage of services. However, health remains a major concern in the area of poverty reduction. The study describes the health status of the population, especially of the poor, and how the sector responds to the needs. Huge inequalities continue to exist with regards to resource allocation, deployment of staff and availability of services among various geographic areas, between the urban and rural population, and between the poor and the non-poor. The study builds upon the existing studies on health and consolidates the sector knowledge. Based on the analysis, the study makes various recommendations on how the health sector reforms can be made more pro-poor by focusing on certain interventions, by targeting certain areas and population groups, by designing new delivery models that would bring the services closer to the population, and by improving financial management to serve the poor more effectively.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; health / saúde; poverty / pobreza

A study of the actual and potential usage of information and communication technology at district and provincial levels in Mozambique with a focus on the health sector - Braa, Jørn; Macome, Esselina; Mavimbe, João Carlos; Nhampossa, José Leopoldo; da Costa, João Leopoldo; José, Bonifacio; Manave, Aurélia; Sitói, António (The Electronic Journal of Information Systems in Developing Countries, 2001)
This article presents results from a study on the use and appropriation of information and communication technologies (ICT) in Mozambique with a focus on the health sector. The three provinces of Gaza, Inhambane and Niassa were surveyed and two questionnaires addressing 1) computer users and their ability to manage ICT, and 2) health workers and their handling of health information, were used. Based on this study appropriate strategies for developing an ICT-infrastructure with the needs of the health sector as points of departure are discussed. The study is born out of a program to strengthen and further develop the health information and management systems at district and provincial levels as part of a process to support decentralisation of the health system in Mozambique. The study shows that computers and Internet are rapidly being spread to the provincial capitals and major districts in Mozambique. A main problem identified is the lack of ICT-skills and education and poorly developed infrastructure and networks of support. There are very few formal ICT companies providing hardware, and even less, software support. Maintenance and learning about ICT are to a large extent going on within informal networks of computer users in the provinces. A main finding in this study is that development of ICT capacity and information systems at district and provincial levels in Mozambique needs to be an integrated effort across sectors. A district health information system cannot be developed in a void. A general recommendation is to develop educational programmes ranging from training of ICT entrepreneurs and health workers and managers, to Masters and PhD programmes in ICT and health information systems. A specific recommendation related to health information systems development is to focus on the district level and to develop a strategy which encompasses and integrates all districts, both the advanced districts with computers and the majority of the districts where there are no computers.
Publisher: Wiley Online Library
Keywords: *indexed; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; health - health information systems / saúde - sistema de informação de saúde; health / saúde

The dynamics of health policies in Mozambique 1975–85 - Walt, Gill; Cliff, Julie (Health Policy and Planning, 1986)
In 1985 Mozambique commemorated its tenth year of independence against a background of a continuing need to defend the country, not only against the actions of the externally-backed Mozambique National Resistance (MNR), but also against drought, acute food shortages and a world economic recession. These external factors have significant implications for the implementation of Mozambique's health policy. The MNR has chosen as deliberate targets for attack: health posts, health centres, rural hospitals, even health workers. Ambushes and the mining of roads and electricity pylons have interrupted the supply and storage of drugs, the maintenance of immunization programmes and the support and supervision of health personnel. Food and water shortages have put lives at risk. These external factors are exacerbating some of the urban and rural class struggles which have become more apparent in the last few years and which, taken together, challenge the direction of health policy. This paper first sets the geographical context of Mozambique's independence. It goes on to explore how health policy was forged through theory and practice over a ten-year period of armed struggle. A brief discussion of health in the colonial state and some of the constraints faced in the first years of independence follows. Finally an attempt is made to assess the effects of both internal struggles and external factors on health policy ten years after independence.
Keywords: *indexed; G - Mozambique / Moçambique; L - english / inglês; health / saúde

Flash Appeal for COVID-19 - Mozambique (United Nationals Office for the Coordination of Humanitarian Affairs (OCHA))
Provides an overview of the COVID-19 situation in Mozambique, details response strategy, coordination, capacity, and constraints. Then goes on to review sectoral impacts, including in internally displaced peoples, education, food security & livelihood, health, nutrition, protection, WASH, and shelter.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; health - COVID-19 / saúde – COVID-19; health / saúde

Mozambique: Covid-19 triples in one week; mining beaches for white paint - Hanlon, Joseph (Mozambique)
New Covid-19 cases triple in one week New Covid-19 cases tripled in less than a week. This is clearly related to people ignoring preventive measures against Covid-19 during the festive season, the director of research at the National Health Institute (INS), Sergio Chicumbe, said Saturday. Crowds
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; GD - Xai-Xai; L - english / inglês; health - COVID-19 / saúde – COVID-19; health / saúde

Organizações não-governamentais denunciam mau atendimento das parturientes nas unidades sanitárias - Joana da Lúcia (CanalMoz, 2021)
Em protesto contra a violência e tratamentos degradantes nas unidades sanitáriasno período pré-natal, de parto, e pós-natal, em todo o país, quarenta organisações não-governamentais reuniram-se na terça-feira, 12 de outubro, para exigir a resposabilização administrativa e criminal das profissionais de saúde que atendem essas mulheres nos hospitais.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health - maternal and child / saúde - materno-infantil; health / saúde

Deviations between the Planned and the Execution Undermine the Health Budget – Observatório do Cidadão para Saúde - Observatório Cidadão para Saúde
In Mozambique, health services are mostly provided by the public sector, and it is the responsibility of the Ministry of Health (MISAU) to enable the creation, planning and control of national health policies. The health sector is the third sector that absorbs most resources from the State Budget (OE), followed by the Education and Infrastructure sectors, according to the methodology presented in the budget documents related to the economic and social sectors. This sector is divided into three levels: namely, the Central Level, which is represented by MISAU; The Provincial Level, which is represented by the Provincial Health Directorates (DPS); and Finally, we have the District Level, which is represented by the Health, Women and Social Action Secretariats (SDSMAS). Therefore, it will be based on these levels that our analysis of allocations to the health sector in the period from 2015 to 2020 will be undertaken.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; health - health services / serviços de saúde